Nanometer metal oxide and preparation method and application thereof
Patent Information
- Application Number
- CN202280096150.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-22
- Publication Date
- 2025-01-14
AI Technical Summary
The existing methods for preparing nanometal oxide materials require high temperature, high pressure or multi-step reaction processes, which limits their low cost and large-scale application. They lack preparation methods with mild conditions, simple reactants and short processes.
The initial alloy containing M, T, and A elements is used to contact the alkali solution through the hydrogen evolution and deT reaction to control the reaction temperature and concentration so that the reaction interface advancement rate reaches no less than 2 μm/min to achieve nano-fragmentation and composition reconstruction. Generates low crystallinity, crystalline or hydrated nano-oxides.
It achieves rapid and simple preparation of nanometal oxides under mild conditions, reduces production costs, improves preparation efficiency, and obtains highly dispersible and diversified nanooxide products, which are suitable for composite materials and other fields.
Smart Images

Figure CN119317602A_ABST
Abstract
Description
Nano metal oxides, their preparation methods and uses Technical field
[0001] This application relates to the technical field of nanomaterials, and particularly to a nano metal oxide, its preparation method and uses. Background technique
[0002] Nano metal oxide materials are widely used in the fields of composite materials, catalytic materials, ceramic materials, refractory materials, advanced electronic materials, battery materials, color-changing materials, wave-absorbing materials, sewage degradation materials, sterilization materials, coatings, pigments, thermal spraying materials, sensors, etc. Currently, the methods for preparing nano metal oxide materials include sol-gel method, alcohol hydrolysis method, forced hydrolysis method, solution gas-phase decomposition method, wet chemical synthesis method, microemulsion method, etc. However, these methods either require harsh equipment and environments such as high temperature and high pressure, or require multiple reactants and go through multiple reaction processes, greatly limiting the low-cost preparation and wide application of nano metal oxide materials. Therefore, it is of great significance to develop a new preparation method for nano metal oxides with mild reaction conditions, simple reactants and short process.
[0003] Summary of the invention
[0004] Based on this, in view of the above problems, it is necessary to provide a preparation method for nano metal oxides with simple process and suitable for large-scale production, which includes the following aspects:
[0005] On the one hand, a preparation method for nano metal oxides includes the following steps:
[0006] Step 1, provide an initial alloy, the initial alloy contains M-type, T-type, and A-type elements; wherein, the M-type elements include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu; the T-type elements include at least one of Al, Zn; the A-type elements include at least one of O, H, Na, K, Mg, Ca, Li, Si; the composition of the initial alloy is mainly A x T y M z , where x, y, z are the atomic percentage contents of the corresponding types of elements, and 0≤x≤15%, 40%≤y≤95%, 5%≤z≤60%, x<z; the solidification structure of the initial alloy is mainly composed of M-T intermetallic compounds;
[0007] Step 2: Carry out the hydrogen evolution and T removal reaction between the initial alloy and the alkali solution. By controlling the temperature and concentration of the alkali solution, make the reaction interface advance inward from the surface of the initial alloy at an average rate not lower than 2 μm / min during the reaction process; during the reaction process, the initial alloy undergoes nano fragmentation through the hydrogen evolution and T removal reaction, and generates a nano-scale M-containing solid product through shape and composition reconstruction; and at least one dimension of the shape of the M-containing solid product does not exceed 500 nm in the three-dimensional direction;
[0008] Step 3: After the hydrogen evolution and T removal reaction ends, collect the M-containing solid product in the reaction system to obtain nano-oxide M, and the nano-oxide M includes at least one of low-crystallinity nano-oxide M, crystalline nano-oxide M, and hydrated nano-oxide M; among them, hydrated nano-oxide M specifically refers to nano-hydroxide M; at least one dimension of the shape of the nano-oxide M does not exceed 500 nm in the three-dimensional direction.
[0009] In the said Step 1,
[0010] Further, the M-type elements include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, Gd;
[0011] Further, the M-type elements include Cr; M includes V; M includes Nb; M includes Ta; M includes W; M includes Mo; M includes Mn;
[0012] Further, the M-type elements include at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu;
[0013] Further, the T-type elements include Al; further, the T-type elements include Zn;
[0014] Further, the A-type elements include at least one of O, Si, Mg; <C
[0015] Further, 0 < x ≤ 15%; further, 0.01% ≤ x ≤ 15%; further, 0.1% ≤ x ≤ 10%; further, 0.3% ≤ x ≤ 10%;
[0016] Further, 45% ≤ y ≤ 94.5%; further, 45% ≤ y ≤ 81%; further, 45% ≤ y ≤ 76%, further, 49% ≤ y ≤ 76%;
[0017] Further, 5% ≤ z ≤ 54.5%; further, 19% ≤ z ≤ 54.5%; further, 24% ≤ z ≤ 54.5%; further, 24% ≤ z ≤ 50%;
[0018] Further, 2x < z;
[0019] Furthermore, the atomic percentage content of the Class A elements in the initial alloy is higher than the content of the Class A elements contained in the initial alloy obtained by smelting ordinary commercially available high-purity T and high-purity M;
[0020] Furthermore, the initial alloy is prepared by solidifying an alloy melt containing T, M, and A elements, and during the solidification process of the alloy melt, a solidification structure mainly composed of MT intermetallic compounds is formed;
[0021] Furthermore, in the initial alloy solidification structure, the type A element exists in the MT intermetallic compound, or the type A element exists in other components other than the MT intermetallic compound, or both situations exist;
[0022] Furthermore, the solidification rate of the initial alloy melt is 0.01K / s to 10 8 K / s; further, the solidification rate of the initial alloy melt is 1K / s~10 8 K / s;
[0023] Furthermore, the MT intermetallic compound refers to an intermetallic compound whose phase composition is an MT intermetallic compound phase, that is, the XRD phase analysis result of the MT intermetallic compound is mainly an MT intermetallic compound;
[0024] Furthermore, the main stoichiometric relationships of M and T in the MT intermetallic compound phase include MT4, MT3, M4T 11 , MT2, M5T8, M3T8, M2T3, MT.
[0025] Furthermore, the MT intermetallic compound phase may also contain other elements besides M and T, such as A-type elements;
[0026] Furthermore, the MT intermetallic compound can be a single phase, such as NbAl3, (Nb-Ta)Al3 intermetallic compound, or a multiphase intermetallic compound composed of different M-type sub-elements and T-type elements, such as a composite multiphase intermetallic compound composed of TaAl3 and YAl3;
[0027] Preferably, the initial alloy does not contain T phase; the T phase is a phase mainly composed of T elements.
[0028] Furthermore, the shape of the initial alloy has an average size in any three-dimensional direction greater than 4 μm;
[0029] Furthermore, the shape of the initial alloy has an average size in any three-dimensional direction greater than 10 μm;
[0030] Furthermore, the average size of any dimension of the initial alloy in the three-dimensional direction is greater than 15 μm;
[0031] Furthermore, the shape of the initial alloy includes at least one of granular, filamentous, strip-shaped, ribbon-shaped, and sheet-shaped;
[0032] Furthermore, the source of the A-type elements in the initial alloy includes at least one of introduction from T raw material, introduction from M raw material, and introduction during the melting process of the initial alloy;
[0033] Furthermore, when 0 < x, in the T raw material, the content of the A-type elements is higher than that in the commercially available high-purity T raw material; for example, taking Al as an example, the impurity content of commercially available high-purity Al is generally less than 0.01%, while the impurity content in commercially available industrial remelted aluminum ingots (Al with lower purity) is generally 0.3% - 1.2%. For example, in the aluminum ingot with the grade Al99.00, the content of Si can reach 0.4%; therefore, this application can use industrial aluminum ingots or aluminum raw materials with lower purity than industrial aluminum;
[0034] Furthermore, when 0 < x, in the M raw material, the content of the A-type elements is higher than that in the commercially available high-purity M raw material; for example, the O impurity content of commercially available high-purity Y is less than 0.1% (atomic ratio); while the O impurity content in commercially available ordinary Y (Y with lower purity) generally exceeds 0.5%; therefore, this application can use commercially available ordinary Y or Y raw materials with lower purity to prepare the initial alloy;
[0035] When the T raw material or the M raw material is a low-purity raw material containing A-type elements, the A-type elements are simultaneously introduced into the alloy melt, so that the initial alloy also contains A-type elements; for example, ordinary rare earth raw materials contain O elements, and industrial remelted aluminum ingots contain Si elements, which will make the initial alloy also contain O and Si elements;
[0036] Furthermore, the A-type elements also originate from the introduction of the atmosphere or the introduction of the furnace lining during the alloy melting process;
[0037] Furthermore, the alloy melting process is carried out in an atmospheric environment;
[0038] Furthermore, when the initial alloy is strip-shaped, it can be prepared by a method including the melt spinning method; [[ID=2,6]]
[0039] Furthermore, when the initial alloy is granular, a relatively large initial alloy ingot can be prepared by the casting method, and then it is broken into initial alloy particles. <00,00426>
[0040] In the second step,
[0041] Further, the alkaline solution comprises at least one of NaOH, KOH, LiOH, RbOH, CsOH, Ba(OH)2, Ca(OH)2, and Sr(OH)2 solutions;
[0042] Furthermore, the solvent in the alkaline solution includes water; preferably, the solvent in the alkaline solution is water;
[0043] Furthermore, the concentration of the alkali in the alkaline solution is 3 to 30 mol / L; further, the concentration of the alkali in the alkaline solution is 5.1 to 30 mol / L; preferably, the concentration of the alkali in the alkaline solution is 5.1 to 15 mol / L; further preferably, the concentration of the alkali in the alkaline solution is 7 to 15 mol / L;
[0044] Furthermore, the alkali in the alkali solution reacting with the initial alloy is in excess dosage, and the volume of the alkali solution is more than 5 times the volume of the initial alloy, so that the reaction can be carried out at a higher alkali concentration.
[0045] Furthermore, the volume of the alkaline solution is more than 10 times the volume of the initial alloy;
[0046] Furthermore, the volume of the alkaline solution is more than 20 times the volume of the initial alloy;
[0047] Furthermore, the reaction temperature range of the initial alloy and the alkaline solution is the temperature of the alkaline solution;
[0048] Furthermore, under certain alkali concentration conditions, the temperature T1 of the alkali solution only needs to be able to ensure that the reaction interface advances inward from the initial alloy surface at an average rate of not less than 2 μm / min during the hydrogen evolution and de-Titanium removal reaction, and that the initial alloy can be nano-fragmented by the hydrogen evolution and de-Titanium removal reaction during the reaction. That is, the temperature T1 and concentration of the alkali solution are determined by the hydrogen evolution and de-Titanium removal reaction rate or the hydrogen evolution and de-Titanium removal reaction time (because the reaction rate is determined by the initial alloy size, the reaction time is also determined; the hydrogen evolution and de-Titanium removal reaction time is the time required for the reaction to produce gas to be unobservable to the naked eye) and the reaction effect. Therefore, when the reaction conditions are limited by the reaction rate value, the temperature T1 value and concentration value range of the alkali solution are also indirectly limited.
[0049] Furthermore, the average rate of 2 μm / min is the critical reaction rate at which the initial alloy can undergo nano-fragmentation through hydrogen evolution and de-T reaction during the reaction process;
[0050] Furthermore, the nano-fragmentation refers to the fragmentation of the initial alloy into a single intermediate product or product with a size of less than 500 nm in at least one dimension in the three-dimensional direction through the hydrogen evolution and de-Ti reaction;
[0051] Furthermore, the nano-fragmentation refers to the fragmentation of the initial alloy into a single intermediate product or product with at least one dimension less than 250 nm in three dimensions through the hydrogen evolution and de-Ti reaction;
[0052] Further, the temperature of the alkaline solution is T1, and T1 ≥ 60°C; further, T1 ≥ 70°C; further, T1 ≥ 80°C; further, T1 ≥ 90°C;
[0053] Furthermore, when M in the initial alloy is mainly composed of one or more elements of Cr, V, Nb, Ta, W, Mo, and Mn, T1 ≥ 60°C;
[0054] Furthermore, when M in the initial alloy is mainly composed of one or more elements of Cr, V, Nb, Ta, W, and Mo, T1 ≥ 60°C;
[0055] Furthermore, when M in the initial alloy is mainly composed of one or more elements of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, T1>100°C;
[0056] Furthermore, when M in the initial alloy contains at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and T contains Zn, T1 ≥ 60°C;
[0057] Furthermore, when M in the initial alloy contains at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and T contains at least one of Al and Zn, 100°C <T1;
[0058] Furthermore, the reaction of the initial alloy with the alkaline solution is carried out under normal pressure or high pressure;
[0059] Furthermore, the reaction of the initial alloy with the alkaline solution is carried out in a closed container;
[0060] In a closed container, when the pressure inside the container exceeds one atmospheric pressure, it is considered high pressure; at the same time, if the gas produced by the reaction in the container cannot be discharged, additional high pressure can also be generated.
[0061] Furthermore, when the reaction is carried out in a sealed container, the initial alloy and the alkaline solution are first placed separately in the sealed container. When the temperature of the alkaline solution reaches the set reaction temperature, the initial alloy is brought into contact with the alkaline solution to carry out the reaction.
[0062] Furthermore, in a closed container, the temperature of the alkaline solution may exceed its boiling point at normal pressure;
[0063] Furthermore, 100°C <T1≤T f溶液 , the reaction of the initial alloy with the alkaline solution is carried out at normal pressure; wherein, T f溶液 is the boiling point temperature of the alkaline solution involved in the reaction under normal pressure; further, the normal pressure refers to the atmospheric pressure when no closed container is used;
[0064] Furthermore, the reaction is carried out under normal pressure, which generally refers to 1 standard atmosphere. At this time, the boiling point of water is 100°C. When alkali is dissolved in water, the boiling point of the aqueous solution of the alkali under 1 standard atmosphere is higher than 100°C, and the higher the concentration of the alkali, the higher its boiling point. For example, the boiling point of a NaOH solution with a molar concentration of 5 mol / L is T f溶液 About 108℃; NaOH solution with a molar concentration of 7 mol / L, boiling point T f溶液 About 112℃; NaOH solution with a molar concentration of 10mol / L, boiling point T f溶液 About 119℃; NaOH solution with a molar concentration of 12mol / L, boiling point T f溶液 About 128℃; NaOH solution with a molar concentration of 15mol / L, boiling point T f溶液 About 140℃; NaOH solution with a molar concentration of 17mol / L, boiling point T f溶液 About 148℃; NaOH solution with a molar concentration of 20mol / L, boiling point T f溶液 About 160℃; NaOH solution with a molar concentration of 25mol / L, boiling point T f溶液 About 180℃; KOH solution with a molar concentration of 10mol / L, boiling point T f溶液 About 125℃; KOH solution with a molar concentration of 12mol / L, boiling point T f溶液 About 136℃; KOH solution with a molar concentration of 15mol / L, boiling point T f溶液 About 150℃;
[0065] Furthermore, 101℃≤T1≤T f溶液 ; Further, 105℃≤T1≤T f溶液 ;
[0066] Furthermore, 101℃≤T f溶液 -5℃≤T1≤T f溶液 ; Further, 101℃≤T f溶液 -2℃≤T1≤T f溶液 ;
[0067] As further preferred, the temperature of the alkaline solution is Tf溶液 , that is, T1=T f溶液 ;
[0068] Since the highest temperature to which the reaction solution can be heated under normal pressure is its boiling point (T f溶液 ). Once the temperature reaches this point, further heating will not increase the solution's temperature; it will simply boil. To increase the reaction temperature, the concentration of the alkaline solution can be increased to achieve a higher boiling point; therefore, controlling the boiling point is the easiest, simplest, and most precise. Furthermore, at the same concentration, reactions at the boiling point require a shorter reaction time than reactions at temperatures below the boiling point.
[0069] T-type elements include at least one of Al and Zn, and Al and Zn are amphoteric metals, which can react with hot concentrated alkaline solutions to become salts and thus dissolve in alkaline solutions; for A-type elements, although they are generally impurity elements in the initial alloy raw materials or the initial alloys, alkali metals or alkaline earth metals such as Na, K, Mg, Ca, and Li are consistent with the cations in the alkaline solution, and they will also become ions and enter the solution; and under normal pressure atmospheric conditions, elements such as O and H are also elements present in alkaline solutions; for Si element, it can also react with hot concentrated alkaline solutions to enter the solution; therefore, both A-type elements and T-type elements can dissolve in hot alkaline solutions.
[0070] Furthermore, during the reaction process of step 2, the initial alloy undergoes nano-fragmentation through a vigorous hydrogen evolution de-Ti reaction, and is then reconstructed in shape and composition to form a nano-scale M-containing solid product. The hydrogen evolution de-Ti reaction is characterized by the dissolution of Ti elements in the initial alloy into the solution while simultaneously releasing hydrogen gas.
[0071] Furthermore, the intensity of the hydrogen evolution and de-TiO reaction is related to the reaction rate of the reaction interface from the initial alloy surface to the inside per unit time. The higher the alkali concentration and the higher the temperature of the alkali solution, the faster the reaction interface advances and the more intense the reaction.
[0072] Furthermore, ultrasound is applied during the hydrogen evolution and de-T reaction to further enhance the nano-fragmentation effect and reaction rate through ultrasound treatment;
[0073] Furthermore, the frequency of the ultrasound is 20kHz~10 6 kHz;
[0074] For example, when the NaOH concentration is 10 mol / L, during the reaction of the initial alloy containing O and Si, which is mainly composed of NbAl3 intermetallic compounds, with the alkaline solution, the rate of advancement of the reaction interface from the initial alloy surface to the inside is as follows:
[0075] When 60°C ≤ T1 ≤ 80°C, the average advancing rate of the reaction interface is about 2 μm / min to 7 μm / min;
[0076] When 80°C ≤ T1 ≤ 90°C, the average advancing rate of the reaction interface is about 7 μm / min to 15 μm / min;
[0077] When 90°C < T1 ≤ 100°C, the average advancing rate of the reaction interface is about 15 μm / min to 30 μm / min;
[0078] When 100°C < T1 ≤ 110°C, the average advancing rate of the reaction interface is about 30 μm / min to 50 μm / min;
[0079] When 110°C < T1 < 119°C, the average advancing rate of the reaction interface is about 50 μm / min to 120 μm / min;
[0080] T 1= T f溶液 When [temperature value], the average advancing rate of the reaction interface is greater than 120 μm / min;
[0081] Furthermore, during the reaction process, the reaction interface advances inward from the initial alloy surface at an average rate of not less than 7 μm / min;
[0082] Furthermore, the reaction interface advances inward from the initial alloy surface at an average rate of not less than 15 μm / min;
[0083] Furthermore, the reaction interface advances inward from the initial alloy surface at an average rate of not less than 30 μm / min;
[0084] Furthermore, under a certain alkali concentration condition, as long as the temperature of the alkali solution can ensure that the reaction interface advances inward from the initial alloy surface at an average rate of not less than 2 μm / min during the hydrogen evolution and T removal reaction process, and the initial alloy can undergo nanoscale fragmentation through the hydrogen evolution and T removal reaction during the reaction process. Therefore, under different initial alloy conditions or alkali solution conditions, when the reaction interface advances at a rate of not less than 2 μm / min during the hydrogen evolution and T removal reaction process, the required reaction solution temperature may be lower than 60°C; especially when assisted by ultrasonic treatment, the required reaction solution temperature may be even lower;
[0085] Furthermore, the occurrence of nanoscale fragmentation means that the initial alloy at the reaction interface is fragmented into nanoscale intermediate products or products through the hydrogen evolution and T removal reaction, and at the same time, nanoscale M-containing solid products are generated through shape and composition reconstruction; during this process, the hydrogen gas violently released by the hydrogen evolution and T removal reaction promotes the nanoscale fragmentation of the intermediate products and products, as well as the diffusion and distribution of the products in the alkali solution after leaving the reaction interface.
[0086] Furthermore, the nano-fragmentation means that the size of the M-containing solid product is smaller than the size of the initial alloy before the nano-fragmentation occurs.
[0087] Furthermore, the shape reconstruction refers to the nano-scale M-containing solid product obtained by the hydrogen evolution and de-T reaction, which is not a simple physical fragmentation of the nanoporous structure (ligament), but a shape change other than physical fragmentation.
[0088] Furthermore, the M-containing solid product has particle dispersibility;
[0089] Furthermore, different valence states of M in the nano-oxidized M correspond to different nano-oxidized M; for example, the oxidized Mn may be MnO or MnO2;
[0090] Furthermore, the size of the M-containing solid product is less than 0.25 times the size of the initial alloy before nano-fragmentation.
[0091] Furthermore, the size of the M-containing solid product is less than 0.05 times the size of the initial alloy before nano-fragmentation.
[0092] Furthermore, the nano-fragmentation refers to the fragmentation of the initial alloy into intermediate products or products with at least one dimension less than 500 nm in the three-dimensional direction through hydrogen evolution and de-Ti reaction during the reaction process;
[0093] Furthermore, the shape of the M-containing solid product has at least one dimension in the three-dimensional direction not exceeding 500 nm;
[0094] Furthermore, the shape of the M-containing solid product has a size of at least one dimension in the three-dimensional direction not exceeding 250 nm;
[0095] Furthermore, the shape of the M-containing solid product has a size of at least one dimension in the three-dimensional direction not exceeding 150 nm;
[0096] Furthermore, the shape of the M-containing solid product includes at least one of a film, a granule, a plate, a strip, a tube, a rod, and a flocculent shape; the flocculent shape refers to a state in which extremely fine microstructures without obvious edges and corners are agglomerated together.
[0097] Furthermore, although the M-containing solid products can be softly aggregated together, they are not tightly connected together through a three-dimensional continuous rigid network structure and maintain the original initial alloy shape.
[0098] Furthermore, when the M-containing solid product is mainly in the form of a thin film, its thickness is 0.25 nm to 30 nm; and the average area of the thin film is greater than 100 nm. 2 ;
[0099] Furthermore, when the M-containing solid product is mainly in granular form, the particle size range is 1.5 nm to 500 nm; preferably 1.5 nm to 200 nm; preferably 1.5 nm to 100 nm;
[0100] Furthermore, when the M-containing solid product is mainly in the form of plates, its thickness ranges from 1.5 nm to 100 nm, preferably from 5 nm to 30 nm, and more preferably from 5 nm to 20 nm; and the average area of the plates is greater than 100 nm. 2 ;
[0101] Furthermore, when the M-containing solid product is mainly in the form of flocs, the size of the floc microstructure is 1 nm to 15 nm;
[0102] Furthermore, when the M-containing solid product is mainly in the form of a tube or rod, it includes a tube or rod, and its diameter ranges from 2 nm to 200 nm; more preferably, from 2 nm to 50 nm; and its aspect ratio is greater than 2; when the aspect ratio is extremely large, the tube or rod can be considered as a fiber;
[0103] Furthermore, the M-containing solid product includes at least one of low-crystallinity nano-oxidized M, crystalline nano-oxidized M, and hydrated nano-oxidized M;
[0104] Furthermore, the low-crystallinity nano-oxide M includes amorphous nano-oxide M;
[0105] Since nano-oxygen hydride M can be regarded as a combination of nano-oxygen hydride M and H2O, nano-oxygen hydride M can be obtained by heating and dehydrating at a relatively low temperature, so the hydrated nano-oxygen hydride M is nano-oxygen hydride M.
[0106] Furthermore, the nano-oxide M can be a single nano-oxide M, or a composite nano-oxide M composed of different M-type sub-elements, such as a composite nano-oxide composed of Y oxide and Ta oxide (Y and Ta are both sub-elements of M-type elements).
[0107] Furthermore, the degree of nano-fragmentation and shape reconstruction is related to the temperature of the alkaline solution. The higher the temperature of the alkaline solution, the higher the degree of fragmentation and the smaller the particle size of the M-containing solid product.
[0108] Furthermore, when it is necessary to enhance the degree of nano-fragmentation, ultrasonic dispersion treatment can be used as an auxiliary treatment;
[0109] Furthermore, when 60 °C ≤ T1 ≤ 100 °C, the degree of nano-fragmentation and shape reconstruction is high, and the degree of fragmentation and shape reconstruction increases with increasing temperature;
[0110] Furthermore, when 100℃ <T1<T f溶液When the nano-fragmentation and shape reconstruction degree are very high, the full fragmentation can be basically achieved;
[0111] As a preference, when T1=T f溶液 When the nano-fragmentation and shape reconstruction are the highest and most complete, the gas expansion caused by the nucleation and growth of a large amount of boiling gas on the solid product at the boiling point greatly promotes the fragmentation and shape reconstruction process.
[0112] Furthermore, during the reaction process, the nanoscale M-containing solid product generated by shape and composition reconstruction will not remain at the original initial alloy reaction interface, but will be further diffused and distributed in the alkaline solution through diffusion and convection of the alkaline solution liquid during its generation;
[0113] Furthermore, the shape and composition reconstruction refers to the fact that the product obtained after the initial alloy hydrogen evolution and de-Ti reaction and nano-fragmentation undergoes a significant change in shape and composition, generating a nano-scale M-containing solid product that is completely different from the initial micron-scale or millimeter-scale alloy composition and shape and is significantly fragmented;
[0114] Furthermore, the generated nano-scale M-containing solid product is not mainly in the shape of a three-dimensional continuous network nanoporous structure or porous skeleton structure;
[0115] It should be noted that the three-dimensional continuous network-like nanoporous structure or porous skeleton structure refers to a nanoporous structure or porous skeleton structure obtained by an ordinary dealloying reaction, and its three-dimensional continuous network-like porous ligaments have three-dimensional rigidity in the three-dimensional direction, and its shape is invariable under the action of gravity or surface tension; the agglomerates formed after the unheat-treated and sintered M-containing solid product particles prepared in this application are agglomerated, and observation under TEM or SEM does not rule out the possibility that they may have characteristics similar to nanoporous structures or porous skeleton structures, but the soft agglomeration connections between the particles are not rigid, and the shape of the agglomerates is variable under the action of gravity or surface tension, and can also be dispersed by a dispersion method.
[0116] Furthermore, the hydrogen evolution and de-Ti reaction converts the initial micron-scale or millimeter-scale alloy into a large number of nano-scale M-containing solid products through a step-by-step nano-fragmentation and shape reconstruction process from the surface to the inside;
[0117] Furthermore, the reaction of the initial alloy with the alkaline solution at a temperature of T1 ≥ 60°C, particularly when T1 > 100°C, is crucial for the preparation of a M-containing solid product with a nanoscale micromorphology. In a comparative example, when an initial alloy powder containing O and Si, primarily composed of NbAl3 intermetallic compounds, was reacted with a 10 mol / L NaOH solution at 25°C for 2 hours at atmospheric pressure (with an average propagation rate at the reaction interface less than 0.5 μm / min), the shape of the initial alloy powder remained largely unchanged before and after the reaction, remaining micron-sized, crushed, and angular powder particles, as shown in Comparative Example 1. Furthermore, when the reaction temperature was lower, the microstructure did not primarily produce a nanoscale, fragmented M-containing solid product, but rather a microscopically rigid nanoporous structure. This nanoporous structure, linked in a three-dimensional network, exhibited an appearance substantially identical to that of the original alloy powder, including angular shapes. Its particle size remained comparable to that of the initial alloy powder, primarily on the micron scale, as shown in Comparative Example 1. Therefore, the reaction between the initial alloy and the alkaline solution at a lower temperature near room temperature is completely different from the reaction in the present application, and the product morphology is also completely different.
[0118] In particular, when the reaction is carried out at normal pressure and at the boiling point of the alkali solution T f溶液When this occurs, the composition of the solution in the reaction system undergoes significant and unique changes. Specifically, in the temperature range below the boiling point of the alkaline solution, the solvent primarily exists as liquid water. However, at or near the boiling point of the alkaline solution, in addition to liquid water and boiling-generated gaseous water, the solvent also contains critical water undergoing a transition from liquid to gaseous water. Furthermore, the presence of reactants and pre-generated nanoscale reaction products in the solution provides a large number of boiling and vaporizing particles, according to the principle of heterogeneous nucleation, placing the reaction system in a unique environment of comprehensive boiling and vaporization. In this special environment, the content and state of atmospheric gases (oxygen and nitrogen) dissolved in the water are also extremely unique (because the hydrogen generated by the reaction of boiling water vapor, T-type elements, and the base changes the saturation partial pressure conditions of the dissolved gases in the water). Specifically, the reaction of MT intermetallic compounds with hot concentrated alkaline solutions generates a large amount of hydrogen during the process of removing the T element from the alloy. This short-lived hydrogen, along with the large amount of water vapor generated by heterogeneous nucleation boiling, acts on the hydrogen evolution and de-T reaction interface, causing a violent expansion that further promotes the continuous nanofragmentation and shape and composition reconstruction of the initial alloy at the reaction interface. Furthermore, the T salt dissolved in the alkaline solution also alters the composition of the reaction solution. These various characteristics of the solution at the boiling point create a very unique boiling-point reaction environment for the reaction. Under these unique reaction conditions, a unique boiling-point reaction process occurs, leading to efficient nanofragmentation and shape and composition reconstruction of the initial alloy through the hydrogen evolution and de-T reaction. This renders the three-dimensional, continuous, nanoporous network typically formed by low-temperature or room-temperature dealloying reactions difficult to maintain. Instead, a nanoscale, fragmented M-containing solid product is generated through this unique nanofragmentation and shape and composition reconstruction process. Due to the constant boiling point of the specific alkaline solution, temperature control can be extremely precise, making the control of product morphology and composition extremely accurate and simple.
[0119] In the step three,
[0120] The time required for the completion of the hydrogen evolution and de-TiO reaction can be judged by whether the hydrogen evolution is complete. When no gas produced by the reaction is observed to be released by the naked eye, the hydrogen evolution and de-TiO reaction can be considered to be complete.
[0121] In addition to the alkali concentration and the temperature of the alkali solution, the reaction time required for complete removal of T and A elements from the initial alloy through the hydrogen evolution-de-T reaction is also related to the shape of the initial alloy: smaller particles or thinner ribbons require a shorter time for the hydrogen evolution-de-T reaction to complete; conversely, a longer time is required. The minimum reaction time t required for the hydrogen evolution-de-T reaction to complete can be calculated based on the average propagation velocity of the reaction interface and the size of the initial alloy. For example, when the initial alloy is in the form of a ribbon with a thickness of d and the average propagation velocity of the reaction interface is v, t = 0.5 d / v, considering that the reaction interface propagates from both the upper and lower surfaces of the ribbon. Similarly, when the initial alloy is in the form of particles with a diameter of d and the average propagation velocity of the reaction interface is v, t = 0.5 d / v.
[0122] In one embodiment, an initial alloy strip of an NbAl3 intermetallic compound containing O and Si reacts with a 10 mol / L boiling-point NaOH solution (boiling point of approximately 119° C.) at an average rate of advancement of the reaction interface of the initial alloy strip of approximately 120 μm / min. This means that a 40 μm thick initial alloy strip can complete the hydrogen evolution and de-Al reaction in 10 seconds; a 20 μm thick initial alloy strip can complete the hydrogen evolution and de-Al reaction in 5 seconds; and even a 5 mm coarse initial alloy particle can complete the hydrogen evolution and de-Al reaction in 21 minutes.
[0123] Further, the reaction time of hydrogen evolution and de-T is 10s to 59min; further, the reaction time of hydrogen evolution and de-T is 10s to 29min; further, the reaction time of hydrogen evolution and de-T is 10s to 9.9min; further, the reaction time of hydrogen evolution and de-T is 10s to 4.9min; further, the reaction time of hydrogen evolution and de-T is 10s to 1min; further, the reaction time of hydrogen evolution and de-T is 10s to 30s;
[0124] Furthermore, the shortest reaction time of hydrogen evolution and T removal can be 10s;
[0125] Obviously, when T1 is higher, the thickness of the initial alloy is thinner or the particle size is smaller, the required reaction time for hydrogen evolution and T removal is shorter; conversely, the reaction time is longer;
[0126] After the hydrogen evolution and de-TiO reaction is complete, continuing to extend the holding time of the reaction system at the original reaction temperature can still ensure that the product is a nano-scale product with particle dispersion. However, if the holding time is long enough, the morphology of the product may change to some extent. In other words, when the reaction time of the initial alloy and the alkaline solution far exceeds the minimum required hydrogen evolution and de-TiO reaction time t, such as several hours, nano-oxidized M can still be obtained, but its morphology may change to some extent.
[0127] Furthermore, the nano-oxidation M has particle dispersibility;
[0128] Furthermore, different valence states of M in the nano-oxidized M correspond to different nano-oxidized M; for example, the oxidized Mn may be MnO or MnO2;
[0129] Furthermore, the size of the nano-oxide M is less than 0.25 times the size of the initial alloy before nano-fragmentation.
[0130] Furthermore, the size of the nano-oxide M is less than 0.05 times the size of the initial alloy before nano-fragmentation; the size refers to the volume size.
[0131] Furthermore, the shape of the nano-oxide M has at least one dimension in the three-dimensional direction not exceeding 500 nm;
[0132] Furthermore, the shape of the nano-oxide M has at least one dimension in the three-dimensional direction that does not exceed 250 nm;
[0133] Furthermore, the shape of the nano-oxide M has at least one dimension in the three-dimensional direction that does not exceed 150 nm;
[0134] Furthermore, the process of collecting the M-containing solid product (nano-oxidized M) includes the separation, collection, cleaning, and drying of the M-containing solid product;
[0135] Furthermore, the separation and collection process of the M-containing solid product includes any one of the following processes a) or b):
[0136] a) adding a large amount of cold solvent (such as water) to the reaction system to rapidly reduce the temperature of the solid product containing M and the alkaline solution in the reaction system described in step 2, while simultaneously reducing the concentration of the alkaline solution in the reaction system, and then separating the diluted and cooled solid and liquid; it is obvious that the alkaline solution with reduced concentration and temperature is safer and also ensures the stability of the product morphology;
[0137] b) filtering the hot alkaline solution and the M-containing solid product in the reaction system together through a filtering device (such as a filter mesh) to separate them, thereby reducing the temperature of the M-containing solid product and achieving solid-liquid separation.
[0138] Furthermore, the cleaning process includes cleaning the M-containing solid product with a dilute acid solution, and the cleaning function includes removing the residual alkali on the M-containing solid product.
[0139] Furthermore, the shape of the nano-oxide M includes at least one of a film, a particle, a plate, a strip, a tube, a rod, and a flocculent shape; the flocculent shape refers to a state in which extremely small microstructures without obvious edges and corners are agglomerated together.
[0140] Furthermore, the shape of the nano-oxide M may vary depending on the reaction conditions, such as the reaction temperature, the time for maintaining the reaction conditions after the hydrogen evolution and dehydrogenation reaction is completed; the shape of the nano-oxide M may change from one shape to another shape, or may not change or may only change slightly; however, no matter how the shape changes, it includes at least one of a film, a granular shape, a plate shape, a strip shape, a tube rod shape, and a flocculent shape;
[0141] Furthermore, although the nano-oxide M can be softly agglomerated together, they are not tightly connected together through a three-dimensional continuous network structure and maintain the original initial alloy shape.
[0142] Furthermore, the shape of the nano-oxide M is completely different from that of the initial alloy, and its particle size is obviously fragmented and reduced;
[0143] Furthermore, when the nano-oxide M is mainly in the form of a thin film, its thickness is 0.25nm to 30nm; and the average area of the thin film is greater than 100nm. 2 ;
[0144] Furthermore, when the nano-oxidation M is mainly in granular form, its particle size ranges from 1.5 nm to 500 nm; preferably from 1.5 nm to 200 nm; preferably from 1.5 nm to 100 nm;
[0145] Furthermore, when the nano-oxidation M is mainly in the form of plates, its thickness ranges from 1.5nm to 100nm, preferably from 5nm to 30nm, and more preferably from 5nm to 20nm; and the average area of the plates is greater than 100nm. 2 ;
[0146] Furthermore, when the nano-oxidation M is mainly in the form of flocs, the size of the floc microstructure is 1 nm to 15 nm;
[0147] Furthermore, when the nano-oxidation M is mainly in the shape of a tube or rod, it includes a tube or rod, and its diameter ranges from 2 nm to 200 nm; more preferably, it ranges from 2 nm to 50 nm; and its aspect ratio is greater than 2; when the aspect ratio is extremely large, the tube or rod can be considered as a fiber;
[0148] Furthermore, the nano-oxide M includes at least one of low-crystallinity nano-oxide M, crystalline nano-oxide M, and hydrated nano-oxide M;
[0149] Furthermore, the low-crystallinity nano-oxide M includes amorphous nano-oxide M;
[0150] Since nano-oxygen hydride M can be regarded as a combination of nano-oxygen hydride M and H2O, nano-oxygen hydride M can be obtained by heating and dehydrating at a relatively low temperature. Therefore, the hydrated nano-oxygen hydride M described in this application is nano-oxygen hydride M.
[0151] Furthermore, the nano-oxide M can be a single nano-oxide M, or a composite nano-oxide M composed of different M-type sub-elements, such as a composite nano-oxide composed of Y oxide and Ta oxide (Y and Ta are both sub-elements of M-type elements).
[0152] In its second aspect, the present application also relates to a method for preparing nano metal oxides, characterized in that the nano metal oxide M prepared by the preparation method in the first aspect is subjected to heat treatment to obtain nano metal oxide M with an improved degree of crystallization.
[0153] Furthermore, the temperature of the heat treatment is 300°C to 2000°C; further, the temperature of the heat treatment is 400°C to 2000°C; further, the temperature of the heat treatment is 500°C to 2000°C;
[0154] Furthermore, the heat treatment time is 1 min to 24 h; further, the heat treatment time is 5 min to 24 h;
[0155] Furthermore, the heat treatment time is 30min to 24h;
[0156] It can be understood that as the heat treatment time is prolonged and the heat treatment temperature is increased, the crystallinity of the heat-treated product is continuously improved until it is completely crystallized.
[0157] Furthermore, during the heat treatment process, changes in the morphology or (and) composition of the nanometal oxide may occur; wherein the composition change includes a change in the valence state of M in the oxide (such as from a low-valent M to a high-valent M) or a change in the atomic arrangement structure of the oxide.
[0158] Furthermore, when the nano-oxide M prepared by the preparation method is crystalline, grain growth will occur after heat treatment;
[0159] Furthermore, when the nano-oxide M prepared by the preparation method is partially crystalline, crystallization and grain growth will occur after heat treatment;
[0160] Furthermore, when the nano-oxide M prepared by the preparation method is amorphous, crystallization and grain growth will occur after heat treatment;
[0161] Furthermore, when the nano-oxide M prepared by the preparation method of one aspect is hydrated nano-oxide M, the hydrated nano-oxide M will be converted into nano-oxide M after heat treatment, and then the nano-oxide M will be crystallized and the grains will grow;
[0162] Furthermore, the nano-oxide M with improved crystallization degree can be a single crystalline nano-oxide M, or a crystalline nano-oxide M composed of different M-type sub-elements, such as a crystalline nano-oxide composed of crystalline oxide Y and crystalline oxide Ta (Y and Ta are both sub-elements of M-type elements).
[0163] Furthermore, during the heat treatment process, the valence state of the M element in the nano-oxide M can change, such as from a low-valence M to a high-valence M;
[0164] Furthermore, the shape of the nano-oxide M with improved crystallinity includes at least one of a film, a granular shape, a plate shape, a strip shape, a tube rod shape, and a sintered agglomerate shape;
[0165] Furthermore, when the nano-oxide M with improved crystallinity is in the form of a thin film, its thickness is 1 nm to 50 nm, and the average area of the thin film is greater than 50 nm. 2 ;
[0166] Furthermore, when the nano-oxide M with improved crystallinity is in the form of particles, its particle size ranges from 3 nm to 500 nm; preferably from 3 nm to 250 nm; more preferably from 3 nm to 150 nm; more preferably from 3 nm to 75 nm;
[0167] Furthermore, when the shape of the nano-oxide M with improved crystallinity is plate-like, its thickness is 3nm to 200nm, preferably 6nm to 75nm, preferably 6nm to 40nm, and the average area of the plate is greater than 100nm. 2 ;
[0168] Furthermore, when the shape of the nano-oxide M with improved crystallinity is strip-shaped, its diameter ranges from 3 nm to 60 nm, and its aspect ratio is greater than 2;
[0169] Furthermore, when the shape of the nano-oxide M with improved crystallinity is a tube-rod shape, it includes a tube-shaped and a rod-shaped shape, and its diameter ranges from 3 nm to 200 nm, and its aspect ratio is greater than 2; when the aspect ratio is extremely large, the tube-rod shape can be considered as a fiber shape;
[0170] Furthermore, when the shape of the nano-oxide M with improved crystallization degree is sintered and agglomerated, its particle size is significantly increased due to sintering and agglomeration, and the particle size range is 5nm to 1mm;
[0171] The crystallinity of the nano-oxide M with increased crystallization degree is related to the heat treatment time and temperature. The higher the temperature and the longer the time, the higher the crystallinity.
[0172] Furthermore, the crystallinity of the nano-oxide M with increased crystallization degree is higher than 50%. Further, the crystallinity of the nano-oxide M with increased crystallization degree is higher than 95%.
[0173] Thirdly, the present application also relates to a preparation method of a nano-metal oxide, which is characterized by comprising the following steps:
[0174] Step 1, providing an initial alloy, the initial alloy containing elements of type M, type T, and type A; wherein, the elements of type M include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu; the elements of type T include at least one of Al, Zn; the elements of type A include at least one of O, H, Na, K, Mg, Ca, Li, Si; the composition of the initial alloy is mainly A x T y M z , where x, y, z are the atomic percentage contents of the corresponding types of elements, and x <0≤x≤15%, 40%≤y≤95%, 5%≤z≤60%, x<z; the solidification structure of the initial alloy is mainly composed of M-T intermetallic compounds;
[0175] Step 2, mixing the initial alloy with an alkali solution at a temperature of T1; wherein, T s溶液 <T1≤T f溶液 T f溶液 is the boiling point temperature of the alkali solution participating in the reaction under normal pressure; T s溶液 is the freezing point temperature of the alkali solution participating in the reaction under normal pressure;
[0176] Step 3, placing the mixture of the initial alloy and the alkali solution in a closed container, and then treating it at a temperature of T2 higher than normal pressure for a period of time, and collecting the product, thus obtaining nano-oxide M whose morphology and / or composition has been modified compared to before the high-pressure treatment; where, T2>T f溶液 ; the nano-oxide M includes at least one of low-crystallinity nano-oxide M, crystalline nano-oxide M, and hydrated nano-oxide M; where, the hydrated nano-oxide M specifically refers to nano-hydroxide M; the shape of the modified nano-oxide M has at least one dimension in the three-dimensional direction not exceeding 500 nm.
[0177] The said Step 1 is completely consistent with Step 1 in the preparation method of a nano-metal oxide described in its first aspect, including the detailed description part corresponding to Step 1. Therefore, the detailed description of Step 1 will not be repeated here.
[0178] In the step 2,
[0179] Further, the alkaline solution comprises at least one of NaOH, KOH, LiOH, RbOH, CsOH, Ba(OH)2, Ca(OH)2, and Sr(OH)2 solutions;
[0180] Furthermore, the solvent in the alkaline solution includes water; preferably, the solvent in the alkaline solution is water;
[0181] Furthermore, the concentration of the alkali in the alkaline solution is 3 to 30 mol / L; further, the concentration of the alkali in the alkaline solution is 5.1 to 30 mol / L; preferably, the concentration of the alkali in the alkaline solution is 5.1 to 15 mol / L; further preferably, the concentration of the alkali in the alkaline solution is 7 to 15 mol / L;
[0182] Furthermore, the alkali in the alkali solution mixed with the initial alloy is an excess dose, and the volume of the alkali solution is more than 5 times the volume of the initial alloy; further, the volume of the alkali solution is more than 10 times the volume of the initial alloy; further, the volume of the alkali solution is more than 20 times the volume of the initial alloy;
[0183] It can be understood that when the initial alloy is mixed with the alkaline solution at a temperature of T1, a hydrogen evolution and dehydrogenation reaction will occur; and the higher the temperature of the alkaline solution and the higher the concentration of the alkaline solution, the faster the reaction rate.
[0184] When the reaction interface advances inward from the initial alloy surface at an average rate of no less than 2 μm / min during the hydrogen evolution dephosphorylation reaction, this constitutes the situation described in step 2 of the first aspect. Details are provided in step 2 of the first aspect. In this case, the initial alloy undergoes nanofragmentation through the hydrogen evolution dephosphorylation reaction, and undergoes shape and composition reconstruction to produce a nanoscale M-containing solid product. This nano-oxidized M undergoes the subsequent high-temperature and high-pressure reaction process of step 3, which can also modify its morphology and / or composition. Therefore, step 2 encompasses the situation described in step 2 of the first aspect, i.e., after the situation described in step 2 of the first aspect, step 3 is performed, which remains within the scope of the third aspect of protection. The modification refers to altering the morphology and / or composition of the nano-oxidized M obtained in step 2; the compositional change includes a change in the valence state of M in the oxidized M (e.g., from a low-valent Mn to a high-valent Mn) or a change in the atomic arrangement structure of the oxidized M.
[0185] When there is Step 3, whether nanomaterial fragmentation occurs in Step 2 or not, or whether the hydrogen evolution and T removal reaction of the initial alloy in Step 2 is completed after mixing with the alkali solution, it will not fundamentally affect the result of the reaction in Step 3. Because the reaction in Step 3 is carried out at a longer time, higher temperature and higher pressure, regardless of the product obtained in Step 2, its morphology or (and) composition will be modified in Step 3.
[0186] Further, in Step 2, the initial alloy and the alkali solution at temperature T1 undergo a hydrogen evolution and T removal reaction while being mixed, and during the hydrogen evolution and T removal reaction process, the reaction interface advances from the surface of the initial alloy inward at an average rate lower than 2 μm / min;
[0187] Further, T s溶液 ≤ T1 < 60 °C; further, T s溶液 ≤ T1 < 80 °C;
[0188] In Step 3,
[0189] Further, in the mixture of the initial alloy and the alkali solution, the degree of the hydrogen evolution and T removal reaction of the initial alloy is not limited; therefore, the solid substance in the mixture can be the initial alloy, or the product after partial or complete hydrogen evolution and T removal reaction of the initial alloy, including the product after sufficient nanomaterial fragmentation or the nanoporous product without sufficient nanomaterial fragmentation;
[0190] The process of placing the mixture of the initial alloy and the alkali solution in a closed container specifically includes at least one of the following two schemes:
[0191] a) Directly place the mixture of the initial alloy and the alkali solution in Step 2 in a closed container, and then treat it at a temperature T2 higher than atmospheric pressure;
[0192] b) First separate the solid substance in the mixture of the initial alloy and the alkali solution in Step 2 from the alkali solution, then mix it with a new alkali solution and place it in a closed container, and then carry out a treatment at a temperature T2 higher than atmospheric pressure; at this time, the new alkali solution can be the same as the original alkali solution or can use other alkali solutions of different types; further, the concentration of the new alkali solution is 0.1 mol / L to 30 mol / L, further, the concentration of the new alkali solution is 5 mol / L to 30 mol / L;
[0193] Further, the pressure is higher than atmospheric pressure but lower than 100 MPa; further, the pressure is higher than atmospheric pressure but lower than 20 MPa;
[0194] Further, T f溶液 < T2 ≤ 500 °C; further, T f溶液 < T2 ≤ 300 °C;
[0195] Further, the treatment time at the temperature T2 higher than normal pressure is 1 minute to 2 hours; further, the treatment time is 1 minute to 30 minutes; further, the treatment time is 1 minute to 10 minutes;
[0196] The process described in step 3 is similar to that of the strong alkali hydrothermal method, both of which are reactions under strong alkali, high temperature, and high pressure conditions, but there are obvious differences between the two: since the precursor used in the strong alkali hydrothermal method is generally a crystalline oxide with low specific surface area, it takes a long time (such as tens of hours) for the OM bond to break first and then recombine to achieve modification; and the modification process of the present application, the precursor used is essentially an alloy raw material. Even if it has become oxide M before modification (mixing process or heating process), in most cases, it is a low-crystalline nano-oxide M with ultra-high specific surface area before modification, or even if it is crystalline nano-oxide M, it is in a state with a high specific surface area; the higher the specific surface area, the higher the metastable energy, which means that the modification is easier; therefore, the heat treatment time required for the modification of the nano-oxide M in the present application is shorter, which reduces energy consumption, improves efficiency, and also obtains products with completely different morphologies. Of course, after the modification is completed and the reaction equilibrium is reached, the modification treatment time is continued to be extended, and the corresponding modified product can also be obtained in this scheme.
[0197] Furthermore, the modified nano-oxide M includes at least one of low-crystallinity nano-oxide M, crystalline nano-oxide M, and hydrated nano-oxide M; wherein the hydrated nano-oxide M specifically refers to nano-hydroxylated M.
[0198] Furthermore, the low-crystallinity nano-oxide M is mainly amorphous nano-oxide M;
[0199] Since nano-oxygen hydride M can be regarded as a combination of nano-oxygen hydride M and H2O, nano-oxygen hydride M can be obtained by heating and dehydrating at a relatively low temperature, so the hydrated nano-oxygen hydride M is nano-oxygen hydride M.
[0200] Furthermore, the crystallinity of the modified nano-oxide M is related to the time, temperature, and pressure of the modification treatment. The higher the temperature, the longer the time, and the higher the pressure, the higher the crystallinity. Therefore, the high temperature and high pressure modification is a method for improving the crystallinity of the modified product while maintaining a high specific surface area of the reaction product without significantly reducing it.
[0201] Furthermore, the shape of the modified nano-oxidation M includes at least one of a film, a flocculent mass, a granular mass, a plate, a strip, and a tube-rod mass;
[0202] Furthermore, different valence states of M in the nano-oxidized M correspond to different nano-oxidized M; for example, the oxidized Mn may be MnO or MnO2;
[0203] Furthermore, the characteristic changes of the modified nano-oxidation M compared to the nano-oxidation M generated after the hydrogen evolution and dehydrogenation reaction include at least one of the following: larger particle size, lower specific surface area, and increased degree of crystallization;
[0204] Furthermore, the M element in the modified nano-oxidized M mainly exists in the high-valent state;
[0205] Furthermore, the degree of crystallization of the modified nano-oxide M is increased by 50% compared to that before the high-pressure treatment; for example, when the degree of crystallization before the high-pressure treatment is 10%; and the degree of crystallization of the modified nano-oxide M is 16%, the degree of crystallization of the modified nano-oxide M is increased by (16%-10%) / 10%=60% compared to that before the high-pressure treatment;
[0206] Furthermore, the degree of crystallization of the modified nano-oxide M exceeds 20%; further, the degree of crystallization of the modified nano-oxide M exceeds 50%;
[0207] Furthermore, the shape of the modified nano-oxide M has at least one dimension in the three-dimensional direction that does not exceed 500 nm.
[0208] Furthermore, when the modified nano-oxidation M is mainly in granular form, its particle size range is 3nm to 500nm; preferably 3nm to 200nm; preferably 3nm to 100nm;
[0209] Furthermore, when the modified nano-oxidation M is mainly in the form of plates, its thickness ranges from 2nm to 120nm, preferably from 5nm to 30nm, and more preferably from 5nm to 20nm; and the average area of the plates is greater than 100nm 2 ;
[0210] Furthermore, when the modified nano-oxidation M is mainly in strip shape, its diameter is 3 nm to 50 nm, and its aspect ratio is greater than 2;
[0211] Furthermore, when the modified nano-oxidation M is mainly in the shape of a tube and a rod, it includes a tube and a rod, and its diameter ranges from 3nm to 200nm; more preferably, it ranges from 3nm to 50nm; and its aspect ratio is greater than 2; when the aspect ratio is extremely large, the tube and rod can be considered as a fiber;
[0212] Furthermore, the modified nano-oxide M can be a single nano-oxide M or a composite nano-oxide M composed of different M-type sub-elements, such as a composite nano-metal oxide composed of Y oxide and Ta oxide (Y and Ta are both sub-elements of M-type elements).
[0213] In its fourth aspect, the present application also relates to a nano metal oxide, characterized in that it is prepared by the preparation method described in any one of the first to third aspects, and its characteristics are detailed in the first to third aspects; its specific characteristics include: the nano metal oxide is nano oxide M, and the M-type element contains at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; the nano oxide M includes at least one of low-crystallinity nano oxide M, crystalline nano oxide M, and hydrated nano oxide M; wherein the hydrated nano oxide M specifically refers to nano hydroxide M; the shape of the nano oxide M has a scale of at least one dimension in the three-dimensional direction not exceeding 500 nm;
[0214] Furthermore, the nano-oxidation M has particle dispersibility;
[0215] Furthermore, different valence states of M in the nano-oxidized M correspond to different nano-oxidized M; for example, the oxidized Mn may be MnO or MnO2;
[0216] Furthermore, the shape of the nano-oxidation M includes at least one of a film, a particle, a plate, a strip, a tube, a rod, and a flocculent shape;
[0217] Furthermore, when the nano-oxide M is mainly in the form of a thin film, its thickness is 0.25nm to 50nm; and the average area of the thin film is greater than 50nm. 2 ;
[0218] Furthermore, when the nano-oxidation M is mainly in granular form, its particle size ranges from 1.5 nm to 500 nm; preferably from 1.5 nm to 200 nm; preferably from 1.5 nm to 100 nm;
[0219] Furthermore, when the nano-oxidation M is mainly in the form of plates, its thickness ranges from 1.5nm to 200nm, preferably from 5nm to 30nm, and more preferably from 5nm to 20nm; and the average area of the plates is greater than 100nm. 2 ;
[0220] Furthermore, when the nano-oxidation M is mainly in the shape of a tube or rod, it includes a tube or rod, and its diameter ranges from 2 nm to 200 nm; and its aspect ratio is greater than 2;
[0221] Furthermore, when the shape of the nano-oxide M is a sintered agglomerate, its particle size increases significantly due to sintering agglomeration, and the particle size ranges from 5 nm to 1 mm;
[0222] In its fifth aspect, the present application also relates to the application of nano metal oxides prepared by the preparation method described in any one of its first to third aspects in composite materials, catalytic materials, ceramic materials, refractory materials, advanced electronic materials, battery materials, color-changing materials, absorbing materials, sewage degradation materials, sterilization materials, coatings, pigments, thermal spray materials, and sensors.
[0223] Furthermore, the present application also relates to the use of nano-chromium oxide prepared by the preparation method described in any one of its first to third aspects in pigments.
[0224] The beneficial effects of this application are mainly reflected in the following aspects:
[0225] First, a low-purity initial alloy raw material composed primarily of MT intermetallic compounds is reacted with an alkaline solution under predetermined reaction conditions, creatively achieving nano-fragmentation of the original initial alloy. Simultaneously, through shape and composition reconstruction, nanoscale nano-oxide M particles with dispersibility are generated. The present application discovered that when the MT intermetallic compound reacts with the alkaline solution at a relatively high temperature, preferably at the boiling point of the alkaline solution, the shape of the initial alloy can be rapidly and completely destroyed, achieving nano-fragmentation of the original initial alloy. Simultaneously, through shape and composition reconstruction, nanoscale nano-oxide M particles with dispersibility are generated. In contrast, products prepared by dealloying at room temperature or lower temperatures are generally nanoporous metal oxides or nanoporous metals that retain the shape of the original initial alloy particles before the reaction, including their angular shapes. As in Comparative Example 1, when an initial NbAl3 intermetallic compound alloy powder containing O and Si reacts with a 10 mol / L NaOH solution at 25°C for 2 hours under normal pressure, the shape of the initial alloy powder remains roughly unchanged before and after the reaction, remaining as the original crushed and angular powder particles. Furthermore, its microstructure does not produce products with particle dispersion such as nanoparticles, nanosheets, or nanorods, but rather a nanoporous structure. This nanoporous structure, connected in a three-dimensional continuous network, has an appearance consistent with the shape of the original initial alloy powder, and its particle size remains comparable to that of the initial alloy powder, primarily on the order of several microns or tens of microns. In the preparation process of the present application, when the average particle size of the initial alloy powder is 10 μm, after nano-fragmentation through the reaction in a concentrated hot alkaline solution, the resulting product is a dispersed nano-sized M oxide with an average particle size of no more than 500 nm. These particles do not contain a nanoporous secondary structure, and these nano-sized M oxides are also dispersible. Although they can be softly agglomerated, they are not tightly and rigidly connected by a three-dimensional continuous network structure to maintain the original initial alloy shape, including the angular shape of the particles. In other words, through the preparation method of the present application, regardless of the shape of the initial alloy, the nano-fragmentation during the reaction process can produce a dispersible nano-sized M oxide product. Therefore, given that the initial alloy strips are relatively thick or the powder particle size is generally large, such as strips generally exceeding 10 μm thick, and the average particle size of the powder particles is generally greater than 5 μm, the reaction of the MT intermetallic compound with an alkaline solution at relatively low temperatures or room temperature generally still produces large nanoporous metal oxides or nanoporous metals in the micrometer range. These products are not suitable for many applications requiring fine particles and good dispersion. In other words, the morphology and size of nanometal oxide powders are key factors affecting the dispersion, fluidity, and reactivity of the powder material. However, this application achieves the preparation of highly dispersible nano-M oxides, which has obvious positive significance.
[0226] Moreover, shape reconstruction occurs at the same time as nano-fragmentation. The shape reconstruction refers to the nanoscale product obtained by the hydrogen evolution and de-T reaction, which is not a simple fragmentation of the nanoporous structure (ligament), but a complete reconstruction. If the low-temperature hydrogen evolution and de-T reaction obtains a nanoporous structure, and the product obtained by the high-temperature hydrogen de-T reaction simply fragments the nanoporous structure, it can only be called a simple fragmentation, and the product morphology is a fragmented porous ligament (ligament). However, in the actual process, the solution described in the present application does not involve such a simple fragmentation, but also includes shape reconstruction; the various morphologies of nano-oxide M, such as lath structure, flocculent structure, and especially film-like structure, cannot be simply obtained by the fragmentation of nanoporous structure ligament (ligament). Therefore, the present application creatively realizes that nano-oxide M does not rely on the formation mechanism of nanoporous structure to form and further simply fragment by regulating the reaction temperature, but is formed by a special fragmentation and complete reconstruction process, which has good theoretical and practical significance.
[0227] While the strong-alkaline hydrothermal method is a relatively mature process for preparing nanometal oxides, it requires a high-pressure reaction vessel. It typically uses inexpensive metal oxide precursors of varying morphologies and a high-concentration strong base (such as NaOH solution) for a prolonged hydrothermal synthesis at high temperatures. The traditional strong-alkaline hydrothermal method for preparing nanometal oxides is characterized by: 1) using inexpensive metal oxide precursors of varying morphologies (the precursors are already metal oxides); 2) being carried out in a high-pressure reaction vessel, requiring sealed, high-pressure conditions; 3) being carried out at relatively high temperatures; and 4) requiring a very long reaction time, measured in hours. In contrast, the present application prepares nano-metal oxides and their subsequent products. Although a strong alkaline solution is also used, it is significantly different from the traditional strong alkaline hydrothermal method: 1) MT intermetallic compounds are mainly used as precursors; 2) The reaction can be carried out in an open container and at normal pressure, and does not necessarily require a high-pressure closed container; 3) It is preferably carried out at the boiling point or near the boiling point temperature of the alkaline solution, and does not need to be carried out at a very high temperature, and the upper limit of the temperature is the boiling point of the alkaline solution, which is very easy to control accurately; 4) The reaction can be completed within a few minutes or even tens of seconds; 5) The MT intermetallic compounds in the initial alloy precursor are nano-fragmented through violent hydrogen evolution and de-T reaction, and are further reconstructed in shape and composition to generate nano-scale nano-oxide M, rather than generating products with nanoporous structures.
[0228] In particular, the M elements Cr, V, Nb, Ta, W, Mo, Mn, and the rare earth elements (Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) in this application were selected after extensive research and are not arbitrary choices. Applicants have discovered that replacing M with elements such as Fe, Co, Ni, Zr, Hf, and Ti results in different reaction processes and products. For example, if M is replaced with Fe, Co, or Ni, the products obtained are mainly nanoporous metal (Fe, Co, or Ni) powders, such as Raney Ni (the alkali solution temperature is generally around 50°C, and the reaction time is generally tens of minutes), rather than nanometal oxides of Fe, Co, or Ni; if M is replaced with Zr or Hf, on the one hand, a clear solution is obtained in step 2, and no nanosolid product containing M is obtained (Zr and Hf will also dissolve in the alkali solution and will not exist as solid substances); if M is replaced with Ti, on the one hand, nanotitanate is obtained in step 3, rather than nanoTiO.
[0229] Secondly, by preferably at the boiling point of the alkali solution T f溶液 The reaction can be precisely controlled. When the concentration of the alkali in the solution is determined, the boiling point to which the solution can be heated at normal pressure is also determined, which means that the pressure and temperature in the reaction conditions are precisely determined. At the boiling point of the alkali solution, any excess heat added to the solution is converted into the heat of vaporization of water without increasing the solution temperature. This allows the solution temperature to be maintained constant at the boiling point by continuous heating. Even if the dealloying process of the MT intermetallic compound generates a large amount of latent heat during the reaction, the temperature of the reaction solution can still be maintained at the boiling point of the solution. Precise control of the reaction temperature ensures precise control of the morphology and composition of the reaction product, which is of great significance. In another aspect, the preparation process of the present application can be carried out in an open container at normal pressure. When the reaction needs to be terminated, cold water or room temperature water can be quickly added to the reaction solution within a few seconds, or cooled through a cold filter. This can almost instantly reduce the temperature and concentration of the reaction system to a temperature and concentration at which the reaction cannot continue, thereby preserving the composition and morphology of the original reaction equilibrium product. Therefore, the solution method provided by the present application can ensure precise control of the morphology and composition of the reaction product. Furthermore, by preferably reacting at or near the boiling point of the alkaline solution, the reaction product can be obtained in a very short time. When the initial alloy is in the form of a thin strip or fine powder, the reaction time can even be less than 1 minute. Therefore, the reaction time of the entire preparation process described in this application is significantly shorter than that required by other reported or published preparation methods, which has a significant positive impact.
[0230] Third, the goal of preparing nano-oxidized M using low-purity M raw materials, low-purity T raw materials, or low-purity initial alloys containing significant amounts of Class A elements is achieved. Specifically, during the reaction, the T- and A-type elements in the initial alloy are primarily dissolved in the alkali concentration and removed through subsequent solid-liquid separation. By utilizing this principle, the goal of preparing high-purity nano-oxidized M products from low-purity initial alloys containing significant amounts of Class A elements is achieved. In particular, the initial alloy has no requirements for controlling the oxygen content, so the initial alloy can be prepared in a low vacuum environment or atmospheric environment, greatly reducing production costs and having a significant beneficial effect.
[0231] Fourth, for certain M-type elements, such as Cr, the present application can prepare low-crystallinity nano-oxide M, including amorphous nano-oxide M. Low crystallinity or amorphous state has two significant advantages: 1) It is a metastable state, thus possessing high energy and thus high activity, resulting in various properties, such as superior catalytic performance. 2) It can undergo controllable crystallization through subsequent heat treatment, resulting in products with varying degrees of crystallinity or complete crystallization. These products can have different properties and applications in different fields.
[0232] Fifth, on the one hand, the present application preferably adopts a reaction temperature of the boiling point of the solution or near the boiling point of the solution (depending on the alkali concentration in the solution, the boiling point is approximately (105 ° C ~ 200 ° C), which is relatively mild; the required initial alloy can be prepared on a large scale by methods such as "alloy smelting + casting + crushing" or "alloy smelting + melt stripping", and the required smelting raw materials can be ordinary purity or low purity M, T and other raw materials. More importantly, the critical reaction time can be as short as tens of seconds to several minutes, which is extremely efficient; and the reaction temperature, pressure and other conditions can be precisely controlled and the reaction can be quickly terminated to obtain the desired product. These features greatly simplify the production process, improve production efficiency, and reduce production costs, making low-cost, efficient and large-scale preparation of each corresponding product possible.
[0233] Sixth, through subsequent heat treatment or modification treatment, the morphology and composition of the prepared nanometal oxide can be further regulated, including changing the product morphology, improving the product crystallinity, increasing the valence state of the M element in the oxide M, etc., so that the obtained product can be used in a variety of application scenarios.
[0234] Therefore, the key innovation of this application lies in the rapid and simple preparation of highly dispersible nanometal oxides using alloys as raw materials. The preparation method of this application is characterized by simplicity, ease of operation, high efficiency, and low cost. Combined with heat treatment, it can produce M-containing nanometal oxides of varying crystallinity, which have promising applications in fields including composite materials, catalytic materials, ceramic materials, refractory materials, advanced electronic materials, battery materials, color-changing materials, wave-absorbing materials, wastewater degradation materials, sterilization materials, coatings, pigments, thermal spray materials, and sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0235] FIG1 is an XRD spectrum of low-crystallinity nano-niobium oxide prepared in Example 1;
[0236] FIG2 is the TEM morphology and diffraction spectrum of low-crystallinity nano-niobium oxide prepared in Example 1;
[0237] FIG3 is the TEM morphology and diffraction spectrum of crystalline nano-niobium oxide obtained by warm heat treatment in Example 1;
[0238] FIG4 is the TEM morphology and diffraction spectrum of crystalline nano-niobium oxide obtained by high-temperature heat treatment in Example 1;
[0239] FIG5 is a TEM low-magnification morphology of a small portion of crystallized nano-vanadium oxide obtained in Example 2;
[0240] FIG6 is a TEM high-magnification morphology and diffraction spectrum of a small portion of crystallized nano-vanadium oxide obtained in Example 2;
[0241] FIG7 is a TEM low-magnification morphology of nano-vanadium oxide obtained in Example 2 after medium-temperature heat treatment;
[0242] FIG8 is a TEM high-magnification morphology and diffraction spectrum of nano-vanadium oxide obtained in Example 2 after medium-temperature heat treatment;
[0243] FIG9 is a TEM high-magnification morphology and diffraction spectrum of crystalline nano-vanadium oxide obtained by high-temperature heat treatment in Example 2;
[0244] FIG10 is a low-magnification TEM morphology and diffraction spectrum of low-crystallinity nano-chromium oxide obtained in Example 3;
[0245] FIG11 is a high-magnification TEM morphology of low-crystallinity nano-chromium oxide prepared in Example 3;
[0246] FIG12 is a low-magnification TEM morphology and diffraction spectrum of crystalline nano-chromium oxide obtained by heat treatment in Example 3;
[0247] FIG13 is a high-magnification TEM image of the crystalline nano-chromium oxide obtained by the warm-heat treatment in Example 3;
[0248] FIG14 is a low-magnification TEM morphology and XRD pattern of crystalline nano-chromium oxide obtained by high-temperature heat treatment in Example 3;
[0249] FIG15 is a high-magnification TEM image of the crystalline nano-chromium oxide obtained by high-temperature heat treatment in Example 3;
[0250] FIG16 is the TEM morphology and diffraction spectrum of the crystalline nano-tantalum oxide obtained in Example 4;
[0251] FIG17 is a high-magnification TEM image of crystalline nano-tantalum oxide obtained in Example 4;
[0252] FIG18 is a low-magnification TEM morphology and diffraction spectrum of low-crystallinity nano-tungsten oxide obtained in Example 5;
[0253] FIG19 is a low-magnification TEM morphology and diffraction spectrum of crystalline nano-tungsten oxide obtained in Example 5;
[0254] FIG20 is a low-magnification TEM morphology and diffraction spectrum of nano-manganese oxide prepared in Example 7;
[0255] FIG21 is a SEM morphology of crystalline nano-manganese oxide obtained by warm heat treatment in Example 8;
[0256] FIG22 is an XRD spectrum of crystalline nano-yttrium oxide obtained in Example 13;
[0257] FIG23 is an XRD spectrum of crystalline nano-gadolinium oxide prepared in Example 15;
[0258] FIG24 is the TEM morphology and diffraction spectrum of crystalline nano-gadolinium oxide prepared in Example 15;
[0259] FIG25 is a SEM photograph of low-crystallinity nano-chromium oxide prepared in Example 16;
[0260] FIG26 is a SEM photograph of the product obtained in Comparative Example 1. DETAILED DESCRIPTION
[0261] The technical solution will be further described below through the following specific embodiments:
[0262] Example 1
[0263] This embodiment provides a method for preparing nano-niobium oxide, comprising the following steps:
[0264] According to Al 75 Nb 25 The nominal formula (atomic percentage) is obtained by smelting commercial low-purity Al raw materials containing O and Si impurities with Nb raw materials to obtain a material mainly composed of Nb. 25 Al 74.5 O 0.15 Si0.35 The alloy melt is prepared by a copper roller strip solidification method to form a 20μm to 30μm thick alloy with an average composition of Nb 25 Al 74.5 O 0.15 Si 0.35 The solidified structure of the initial alloy strip is primarily composed of NbAl3 intermetallic compounds. (The nominal formula refers to the approximate composition or formula without considering impurities; the actual melt composition after smelting will be slightly different; the nano-niobium oxide is equivalent to nano-Nb oxide.)
[0265] Under normal pressure, 0.5g of the above Nb 25 Al 74.5 O 0.15 Si 0.35 The initial alloy ribbons were reacted with 50 mL of a 10 mol / L NaOH solution at its boiling point (~119°C) at atmospheric pressure with constant stirring. Within 1 minute, the hydrogen evolution de-Al reaction was complete, and the initial alloy ribbons were nano-fragmented by the hydrogen evolution de-Al reaction, with the shape and composition reconstructed to form a nanoscale solid product.
[0266] One minute after the start of hydrogen evolution and Al removal, 500 mL of water at 20°C was poured into the reaction system to reduce the concentration of the alkaline solution to below 1 mol / L and the temperature to below 40°C. The solid product was further separated from the diluted alkaline solution, and the residual alkali adsorbed by the solid product was neutralized and cleaned with a 0.01 mol / L dilute hydrochloric acid solution. After separation and drying, a powder mainly composed of low-crystallinity nano-Nb oxide (or Nb hydroxide) was obtained. Its XRD pattern is shown in Figure 1, and its TEM morphology and diffraction spectrum are shown in Figure 2. The TEM morphology shows that it is composed of a large amount of flocs; the flocs have a particle size range of 1 nm to 15 nm (see the inset of Figure 2);
[0267] The low-crystallinity nano-Nb oxide was heat-treated at 600°C for 2h to obtain nano-Nb oxide with a particle size of 3nm to 150nm, which had a significantly improved degree of crystallization but was not completely crystallized. The TEM morphology of the obtained nano-Nb oxide is shown in FIG3 .
[0268] The low-crystallinity nano-Nb oxide was heat-treated at 900°C for 2h to obtain crystalline nano-Nb oxide with a particle size of 3nm to 300nm. Its TEM morphology and diffraction spectrum are shown in Figure 4. During the heat treatment and sintering process, some Nb oxide particles merged and grew. The heat-treated crystalline nano-Nb oxide was ball-milled to obtain dispersed nano-Nb oxide.
[0269] Example 2
[0270] This embodiment provides a method for preparing nano-vanadium oxide, comprising the following steps:
[0271] According to Al 75 V 25 The nominal formula (atomic percentage) is obtained by melting commercially available low-purity Al raw materials containing O and Si impurities with V raw materials to obtain a V-based material. 24.9 Al 74.6 O 0.2 Si 0.3 The alloy melt is prepared into V by a casting method 24.9 Al 74.6 O 0.2 Si 0.3 An alloy ingot mainly composed of a VAl3 intermetallic compound phase; the alloy ingot is further crushed by a mechanical crushing method into an initial alloy powder with an average particle size not exceeding 50 μm;
[0272] Under normal pressure, 0.5g of the above-prepared V 24.9 Al 74.6 O 0.2 Si 0.3 The initial alloy powder reacted with 50 mL of a 12 mol / L NaOH solution at its boiling point (~128°C) under atmospheric pressure with constant stirring. Within 1 minute, the hydrogen evolution de-Al reaction was complete, and the initial alloy was nano-fragmented by the hydrogen evolution de-Al reaction. Simultaneously, the shape and composition of the nano-scale solid product was reconstructed.
[0273] 2 minutes after the start of the reaction, the solid product and the alkaline solution in the reaction system are separated by a multi-layer metal filter and the solid product is cooled to below 40°C. The residual alkali adsorbed by the solid product is then neutralized and cleaned with a 0.02 mol / L dilute hydrochloric acid solution. After separation and drying, a small amount of crystalline nano-V oxide powder is obtained. The obtained nano-V oxide powder is mainly in the form of flocculent and thin films, wherein the thickness of the film is 2nm to 15nm and the average area is greater than 200nm. 2 The particle size of the flocculent structure ranges from 1 nm to 15 nm, and its TEM morphology and diffraction spectrum are shown in Figures 5 and 6;
[0274] The above-mentioned small amount of crystallized nano-V oxide was heat-treated at 600℃ for 2h to obtain the majority of crystallized nano-V oxide; its shape was mainly thickened film and granular, wherein the thickness of the film was 3nm~25nm, and the average area was greater than 200nm. 2 The particle size range of the granules is 5nm to 50nm, and its TEM morphology and diffraction spectrum are shown in Figures 7 and 8;
[0275] The above-mentioned small amount of crystallized nano-V oxide was heat-treated at 900°C for 2h to obtain crystalline nano-V oxide; its shape was mainly short rod particles with a diameter of 10nm to 100nm. Its TEM morphology and diffraction spectrum are shown in Figure 9.
[0276] Example 3
[0277] This embodiment provides a method for preparing nano-chromium oxide, comprising the following steps:
[0278] According to Al 80 Cr 20 The nominal formula (atomic percentage) is obtained by smelting the commercially available low-purity Al raw material containing O and Si impurities with the Cr raw material to obtain a Cr 20 Al 79.5 O 0.1 Si 0.4 The alloy melt is solidified into an alloy ingot, which is then crushed into particles with an average particle size of 100 μm and a main component of Cr 20 Al 79.5 O 0.1 Si 0.4 The initial alloy powder has a solidified structure mainly composed of CrAl4 intermetallic compounds.
[0279] Under normal pressure, Cr 20 Al 79.5 O 0.1 Si 0.4 The initial alloy powder reacts with NaOH solution and is stirred continuously; the concentration of NaOH solution is 12 mol / L, the temperature is its boiling point under normal pressure (~128°C), and the volume of NaOH solution is Cr 20 Al 79.5 O 0.1 Si 0.4 The volume of the initial alloy powder is about 100 times; within 1.5 minutes, the hydrogen evolution and Al removal reaction is completed, and Cr 20 Al 79.5 O 0.1 Si 0.4 The initial alloy powder is nano-fragmented through hydrogen evolution and de-Al reaction, and simultaneously undergoes shape and composition reconstruction to generate nano-scale solid flocculent products;
[0280] Two minutes after the start of the hydrogen evolution and de-Al reaction, 10 times the volume of the reaction solution and water at 20°C was added to the reaction system to reduce the concentration of the alkaline solution to below 1.2 mol / L and the temperature to below 40°C. The resulting solid flocculent product was separated from the diluted alkaline solution, and the residual alkali adsorbed by the solid product was neutralized and cleaned with a 0.01 mol / L dilute hydrochloric acid solution. After separation and drying, a low-crystallinity nano-chromium oxide powder was obtained, consisting of amorphous nano-chromium oxide or amorphous chromium hydroxide. Its TEM morphology and diffraction spectrum are shown in Figures 10 and 11. It can be seen that its morphology is mainly composed of extremely fine flocculent microstructures with a particle size range of 1.0 nm to 15 nm. This flocculent structure is not a rigid nanoporous structure, but rather a flat and dispersed flocculent structure.
[0281] Two minutes after the start of the hydrogen evolution and de-Al reaction, the collected powder, mainly composed of low-crystallinity nano-Cr oxide, was heat-treated at 600°C for 2 hours to obtain crystalline nano-Cr oxide particles with a particle size of 3 nm to 100 nm. The TEM morphology and diffraction spectrum of the obtained particles are shown in Figures 12 and 13. It can be seen that after the crystallization by medium-temperature heat treatment, the particles still have good dispersion.
[0282] Two minutes after the start of the hydrogen evolution de-Al reaction, the collected powder, primarily composed of low-crystallinity nano-chromium oxide, was heat-treated at 900°C for 2 hours to obtain crystalline nano-chromium oxide particles with a particle size of 3nm to 150nm. Their TEM morphology, XRD spectrum, and diffraction spectrum are shown in Figures 14 and 15. It can be seen that even after high-temperature heat treatment and crystallization, the crystalline nano-chromium oxide particles exhibit sintering and agglomeration. However, the particles still have good dispersion or porosity, and their sintered structure is a loose structure similar to nanoporous. This dispersion and porosity allow the particles to be further crushed and refined along the grain boundaries through subsequent sand milling and ball milling, thereby obtaining ultrafine spherical or near-spherical nano-chromium oxide particles. Since most other traditional methods for producing commercial nano-chromium oxide generally produce solid, large particle agglomerates or coarse powders, which lack the loose structure of nanoporous fine powders, it is difficult to further break them up through subsequent sand milling and ball milling to obtain ultrafine spherical or near-spherical nano-chromium oxide particles. Therefore, this embodiment can produce crystalline nano-chromium oxide with excellent particle dispersibility and looseness, which has great application potential.
[0283] One minute after the start of the hydrogen evolution de-Al reaction, the alkali solution and the solid product of the reaction system are directly poured into a sealed reactor. The temperature of the reactor and its interior is raised to 250°C and kept warm for 20 minutes. In a sealed environment, the pressure in the reactor is higher than normal pressure. After keeping warm for 20 minutes, the temperature and pressure are lowered, and the product in the reactor is subjected to solid-liquid separation. After cleaning and drying, the modified nano-chromium oxide with significantly improved crystallinity is obtained. The morphology of the nano-chromium oxide is mainly granular, and the particle size ranges from 3 nm to 100 nm.
[0284] The low-crystallinity nano-chromium oxide, crystalline nano-chromium oxide, and modified nano-chromium oxide can all be applied to the fields of pigments, coatings, ceramic materials, refractory materials, electronic materials, and composite materials.
[0285] Example 4
[0286] This embodiment provides a method for preparing nano-tantalum oxide, comprising the following steps:
[0287] According to Al 75 Ta 25 The nominal formula (atomic percentage) is obtained by melting commercially available low-purity Al raw materials containing O and Si impurities with Ta raw materials to obtain a composition mainly composed of Ta. 24.5 Al 74.5 O 0.5 Si 0.5 (atomic percentage) of uniform alloy melt, the alloy melt was prepared by copper roller strip solidification method to a thickness of 25 μm, the composition of Ta 24.5 Al 74.5 O 0.5 Si 0.5 The initial alloy strip is mainly composed of TaAl3 intermetallic compound phase.
[0288] Under normal pressure, 0.5g of the Ta 24.5 Al 74.5 O 0.5 Si 0.5 The initial alloy ribbons were reacted with 50 mL of a 12 mol / L NaOH solution at its boiling point (~128°C) at atmospheric pressure with constant stirring. Within 100 seconds, the hydrogen evolution de-Al reaction was complete, and the initial alloy ribbons were nano-fragmented by the hydrogen evolution de-Al reaction. Simultaneously, their shape and composition were reconstructed to form a nanoscale Ta-containing solid product.
[0289] Two minutes after the start of the reaction, the solid product was separated from the solution, washed, and dried to obtain a Ta-containing solid powder, the composition of which was crystalline nano-Ta oxide. Its TEM morphology and diffraction spectrum are shown in Figures 16 and 17. It can be found that this embodiment can directly obtain crystalline nano-Ta oxide particles with very good particle dispersibility and a particle size of 3 nm to 100 nm.
[0290] Example 5
[0291] This embodiment provides a method for preparing nano-tungsten oxide, comprising the following steps:
[0292] According to Al 80 W 20 The nominal formula (atomic percentage) is obtained by smelting commercially available low-purity Al raw materials containing Si impurities and W raw materials to obtain a W-based raw material. 20 Al 79.5 Si 0.5 (atomic percentage) of alloy melt, the alloy melt is solidified into an ingot, and then crushed into an initial alloy powder with an average particle size of 50 μm, which is mainly composed of a WAl4 intermetallic compound phase.
[0293] Under normal pressure, W 20 Al 79.5 Si 0.5 The initial alloy powder reacts with a NaOH aqueous solution and is continuously stirred; wherein the concentration of the NaOH solution is 10 mol / L, the temperature is its boiling point at atmospheric pressure (~119°C), and the volume of the NaOH solution is W 20 Al 79.5 Si 0.5 The volume of the initial alloy powder is about 100 times that of the initial alloy powder. Within 1 minute, the hydrogen evolution de-Al reaction is completed, and the initial alloy powder is nano-fragmented by the hydrogen evolution de-Al reaction, and at the same time, the shape and composition are reconstructed to form a nano-scale W-containing solid product.
[0294] 2 minutes after the reaction started, the solid product was separated from the solution, and after washing and drying, low-crystallinity nano-W oxide particles were obtained, whose TEM morphology and diffraction spectrum are shown in FIG18 ; the particle size range is 3 nm to 100 nm.
[0295] The low-crystallinity nano-W oxide was heat-treated at 600°C for 2h to obtain crystalline nano-W oxide particles with a particle size range of 10nm to 400nm. The TEM morphology and diffraction spectrum of the obtained particles are shown in FIG19 . During the heat treatment and sintering process, some W oxide particles merged and grew. The heat-treated crystalline nano-W oxide was sand-milled to obtain dispersed nano-W oxide.
[0296] Example 6
[0297] This embodiment provides a method for preparing nano-molybdenum oxide, comprising the following steps:
[0298] According to Al 77 Mo 23 The nominal formula (atomic percentage) is obtained by smelting commercial Al raw materials and Mo raw materials containing O impurities to obtain a Mo-based material with a main component of Mo. 23 Al 76.95 O 0.05 (atomic percentage) alloy melt, the alloy melt was prepared by a copper roller strip rapid solidification method to a thickness of 25 μm, the composition of Mo 23 Al 76.95 O 0.05 The solidified structure of the initial alloy strip is mainly composed of two intermetallic compounds: MoAl4 and Mo3Al8.
[0299] Under normal pressure, Mo 23 Al 76.95 O 0.05 The initial alloy strip reacts with KOH aqueous solution and is stirred continuously; wherein the concentration of KOH solution is 15 mol / L, the temperature is its boiling point under normal pressure (~150°C), and the volume of KOH solution is Mo 23 Al 76.95 O 0.05 The volume of the initial alloy strip is about 50 times that of the initial alloy strip. Within 1 minute, the hydrogen evolution de-Al reaction is completed, and the initial alloy is nano-fragmented by the hydrogen evolution de-Al reaction, and simultaneously the shape and composition are reconstructed to form a nano-scale solid flocculent product.
[0300] Two minutes after the reaction begins, the solid flocculent product is separated from the solution, and the residual alkali adsorbed by the solid product is neutralized and cleaned with a 0.02 mol / L dilute hydrochloric acid solution. After separation and drying, a low-crystallinity nano-Mo oxide powder is obtained, which is composed of amorphous nano-Mo oxide or amorphous Mo hydroxide. The morphology of the powder is mainly composed of extremely fine flocculent microstructures, and the particle size of the flocculent microstructure ranges from 1.0 nm to 10 nm.
[0301] The low-crystallinity nano Mo oxide powder is heat-treated at 600° C. for 2 hours to obtain crystalline nano Mo oxide particles with a particle size of 3 nm to 100 nm.
[0302] Example 7
[0303] This embodiment provides a method for preparing nano manganese oxide, comprising the following steps:
[0304] According to Al 73.3 Mn 26.7 The formula (atomic percentage) is obtained by melting Al raw materials and Mn raw materials, and the main components are Al73.3 Mn 26.7 The alloy melt was prepared into an Al2O3 sheet with a thickness of 25 μm by a copper roller strip solidification method. 73.3 Mn 26.7 The initial alloy strip, which is mainly composed of Al 11 Mn4 intermetallic compound phase composition.
[0305] At normal pressure, Al 73.3 Mn 26.7 The initial alloy strip reacts with NaOH aqueous solution and is stirred continuously; wherein the concentration of the NaOH solution is 12 mol / L, the temperature is its boiling point at normal pressure (~128°C), and the volume of the NaOH solution is Al 73.3 Mn 26.7 The volume of the initial alloy strip is about 75 times; within 1 minute, the hydrogen evolution and de-Al reaction is completed, and Al 73.3 Mn 26.7 The initial alloy ribbons are nano-fragmented through hydrogen evolution and de-Al reaction, and simultaneously undergo shape and composition reconstruction to generate nano-scale solid products.
[0306] Two minutes after the start of the hydrogen evolution and de-Al reaction, the solid product was separated from the solution, and after washing, separation, and drying, partially crystallized nano-Mn oxide was obtained (see the upper left diffraction inset of Figure 20). Its shape was mainly plate-like particles (see Figure 20), and also included some thin film structures (see the lower left inset of Figure 20); the thickness of the plate-like particles ranged from 3nm to 150nm, and the diameter of the plate was from 5nm to 500nm; the thickness of the film was from 1nm to 20nm, and the average area was greater than 100nm. 2 .
[0307] Example 8
[0308] This embodiment provides a method for preparing nano manganese oxide, comprising the following steps:
[0309] According to Al 73.3 Mn 26.7 The nominal formula (atomic percentage) is obtained by smelting commercially available low-purity Al raw materials containing Si impurities and Mn raw materials to obtain a composition mainly composed of Al 73.3 Mn 26.5 Si 0.2 The alloy melt was prepared into an Al2O3 sheet with a thickness of 25 μm by a copper roller strip solidification method. 73.3 Mn 26.5 Si 0.2 The initial alloy strip, which is mainly composed of Al 11 Mn4 intermetallic compound phase composition.
[0310] At normal pressure, Al73.3 Mn 26.5 Si 0.2 The initial alloy strip reacts with NaOH aqueous solution and is stirred continuously; wherein the concentration of NaOH solution is 10 mol / L, the temperature is 105℃~115℃, and the volume of NaOH solution is Al 73.3 Mn 26.5 Si 0.2 The volume of the initial alloy strip is about 75 times; within 1 minute, the hydrogen evolution and de-Al reaction is completed, and Al 73.3 Mn 26.5 Si 0.2 The initial alloy strips are nano-fragmented through hydrogen evolution and de-Al reaction, and simultaneously undergo shape and composition reconstruction to generate nano-scale solid flocculent products.
[0311] The reaction conditions are maintained for 2 hours and the concentration of the alkaline solution is maintained by adding water, so that the solid flocculent product generated by the hydrogen evolution and de-Al reaction further undergoes morphological changes under the original reaction temperature and reaction environment; the obtained solid product is separated from the solution, washed, and dried to obtain partially crystallized nano-Mn oxide, which mainly has a plate-like shape, and the plate thickness ranges from 3 nm to 75 nm and the plate diameter ranges from 3 nm to 300 nm;
[0312] The partially crystallized nano-Mn oxide was heat treated at 600°C for 2h to obtain nearly completely crystallized nano-Mn oxide in which the valence state of Mn changed from low valence to high valence. The SEM morphology of the obtained nano-Mn oxide particles is shown in FIG21 . The shape of the obtained nano-Mn oxide particles is mainly plate-like, including some plate-like hexagonal particles, and the thickness of the plate ranges from 3nm to 150nm, and the plate diameter is 5nm to 500nm.
[0313] Example 9
[0314] This embodiment provides a method for preparing nano-vanadium oxide, comprising the following steps:
[0315] According to Zn 75 V 25 (atomic percentage) of the formula is melted to obtain the main component of Zn 75 V 25 The alloy melt is solidified into an alloy ingot, and then crushed into an initial alloy powder with an average particle size of 50 μm, which is mainly composed of a VZn3 intermetallic compound phase.
[0316] Under normal pressure, 0.25g of the above-prepared Zn 75 V 25The initial alloy powder reacted with 50 mL of a 15 mol / L NaOH solution at its boiling point (~140°C) under atmospheric pressure with constant stirring. Within 1 minute, the hydrogen evolution and dezincification reaction was complete, and the initial alloy was nano-fragmented by the hydrogen evolution and dezincification reaction. Simultaneously, the shape and composition of the nano-scale solid flocculent product was reconstructed.
[0317] 10 minutes after the reaction started, the solid flocculent product was separated, washed and dried to obtain a small amount of crystalline nano-V oxide powder. The powder shape was mainly flocculent, and the particle size of the flocculent microstructure ranged from 1.0 nm to 15 nm.
[0318] Example 10
[0319] This embodiment provides a method for preparing nano-chromium oxide, comprising the following steps:
[0320] According to Al 61 Cr 39 The nominal formula (atomic percentage) is obtained by smelting commercial Al raw materials and Cr raw materials, which mainly consists of Al 60.7 Cr 39 O 0.1 Si 0.2 The alloy melt is solidified into an alloy ingot, and then crushed into an initial alloy coarse powder with an average particle size of about 2 mm, which is mainly composed of an Al8Cr5 intermetallic compound phase.
[0321] At normal pressure, Al 60.7 Cr 39 O 0.1 Si 0.2 The initial alloy coarse powder reacts with NaOH aqueous solution and is stirred continuously; wherein the concentration of NaOH solution is 12 mol / L, the temperature is its boiling point under normal pressure (~128 ° C), and the volume of NaOH solution is Al 60.7 Cr 39 O 0.1 Si 0.2 About 50 times the volume of the initial alloy coarse powder;
[0322] Within 8 minutes after the reaction started, the hydrogen evolution and Al removal reaction was completed. 60.7 Cr 39 O 0.1 Si 0.2 The initial alloy coarse powder is nano-fragmented through hydrogen evolution and de-Al reaction, and simultaneously undergoes shape and composition reconstruction to generate nano-scale solid flocculent products;
[0323] 10 minutes after the reaction started, the solid flocculent product was separated, washed and dried to obtain low-crystallinity nano-chromium oxide powder. The powder shape was mainly flocculent, and the particle size of the flocculent microstructure ranged from 1.0 nm to 15 nm.
[0324] The powder mainly composed of low-crystallinity nano-chromium oxide is heat-treated at 600° C. for 2 hours to obtain crystalline nano-chromium oxide particles with a particle size of 3 nm to 100 nm;
[0325] The powder mainly composed of nano-chromium oxide with low crystallinity is heat-treated at 900° C. for 2 hours to obtain crystalline nano-chromium oxide particles with a particle size of 3 nm to 150 nm.
[0326] The above Al 60.7 Cr 39 O 0.1 Si 0.2 The initial alloy coarse powder and 50 volumes of a 12 mol / L NaOH aqueous solution were placed in a sealed autoclave. The autoclave and its interior were then heated to 250°C and held at this temperature for 20 minutes. In a sealed environment, the pressure within the autoclave was maintained above atmospheric pressure. After 20 minutes of holding, the pressure and temperature were reduced, and the modified solid product was collected. After washing and drying, the modified partially crystallized nano-chromium oxide was obtained. Its morphology mainly consisted of tubular rods and granules. The tubular rods had a diameter of 2nm-10nm and an aspect ratio greater than 2. The granules had a particle size range of 2nm-100nm.
[0327] The low-crystallinity nano-chromium oxide, crystalline nano-chromium oxide, and modified nano-chromium oxide can all be applied to the fields of pigments, coatings, ceramic materials, refractory materials, electronic materials, and composite materials.
[0328] Example 11
[0329] This embodiment provides a method for modifying nano-vanadium oxide, comprising the following steps:
[0330] According to Al 75 V 25 The nominal formula (atomic percentage) is obtained by melting commercially available low-purity Al raw materials containing O and Si impurities with V raw materials to obtain a V-based material. 24.9 Al 74.6 O 0.2 Si 0.3 The alloy melt is prepared into a composition of V by a casting method 24.9 Al 74.6 O 0.2 Si 0.3An alloy ingot mainly composed of a VAl3 intermetallic compound phase is prepared. The alloy ingot is further crushed by mechanical crushing to form an initial alloy powder with an average particle size not exceeding 50 μm;
[0331] Under normal pressure, 0.5g of the above-prepared V 24.9 Al 74.6 O 0.2 Si 0.3 The initial alloy powder is mixed with 50 mL of NaOH solution; the concentration of the NaOH solution is 12 mol / L, and the temperature is its boiling point at atmospheric pressure (~128°C). One minute after the reaction begins, the solid product and the reaction base solution in the reaction system are poured into a sealed autoclave. The autoclave, along with the solid product and base solution, is then heated to 300°C and held at this temperature for 10 minutes. In this sealed environment, the pressure within the autoclave is higher than atmospheric pressure. After 10 minutes of holding, the pressure and temperature are reduced, and the modified solid product is collected. After washing and drying, the modified nano-V oxide is obtained, which is primarily crystalline and has a morphology consisting primarily of short rods and particles. The short rods have a diameter of 2nm-30nm, and the particles have a size range of 5nm-200nm.
[0332] Example 12
[0333] This embodiment provides a method for preparing nano-niobium oxide, comprising the following steps:
[0334] According to Al 75 Nb 25 The nominal formula (atomic percentage) is obtained by smelting commercial low-purity Al raw materials containing O and Si impurities with Nb raw materials to obtain a material mainly composed of Nb. 25 Al 74.7 O 0.1 Si 0.2 The alloy melt was prepared into a molten alloy with a thickness of 25 μm and a composition of Nb by a copper roller strip solidification method. 25 Al 74.7 O 0.1 Si 0.2 The solidified structure of the initial alloy strip is mainly composed of NbAl3 intermetallic compounds.
[0335] Under normal pressure, 0.5g of the Nb 25 Al 74.7 O 0.1 Si 0.2 The initial alloy strips reacted with 50 mL of a 12 mol / L NaOH solution at 60°C with constant stirring. Within 7 minutes, the hydrogen evolution de-Al reaction was complete, and the initial alloy fragmented and reconstructed in shape and composition to form a nanoscale solid product.
[0336] Eight minutes after the reaction begins, the solid product and the reaction alkaline solution are poured into a sealed autoclave. The autoclave, along with the solid product and alkaline solution, is then heated to 200°C and held at this temperature for one hour. In this sealed environment, the pressure within the autoclave is maintained above atmospheric pressure. After one hour of holding, the pressure and temperature are reduced, and the modified solid product is collected. After washing and drying, the modified nano-NbO2 is obtained. The product is primarily crystalline and has a morphology consisting primarily of short rods and granules. The short rods have diameters ranging from 2 nm to 10 nm, while the granules have a size range of 2 nm to 75 nm.
[0337] Example 13
[0338] This embodiment provides a method for preparing nano-yttrium oxide, comprising the following steps:
[0339] According to Al 50 Y 50 The nominal formula (atomic percentage) is obtained by melting commercial Al raw materials and Y raw materials containing O to obtain a composition mainly composed of Y 50 Al 49.5 O 0.5 The alloy melt is prepared into a 200 μm thick alloy by a copper roller strip solidification method. The main components are Y 50 Al 49.5 O 0.5 The initial alloy rapid solidification sheet, its solidification structure is mainly composed of YAl intermetallic compounds.
[0340] Under normal pressure, 0.5g of the Y 50 Al 49.5 O 0.5 The initial alloy quick-setting sheet was reacted with 50 mL of NaOH solution and stirred continuously, wherein the concentration of the NaOH solution was 10 mol / L and the temperature was the boiling point at normal pressure (~119°C); within 2 minutes, the hydrogen evolution and Al removal reaction was completed, and Y 50 Al 49.5 O 0.5 The initial alloy rapid solidification sheet is nano-fragmented through hydrogen evolution and de-Al reaction, and simultaneously undergoes shape and composition reconstruction to generate nano-scale Y-containing solid products.
[0341] 3 minutes after the start of the reaction, the Y-containing solid product was separated from the alkaline solution, washed, and dried to obtain nano-Y oxide powder, which was mainly crystalline, granular, and had a particle size of 3 nm to 350 nm. Its XRD spectrum is shown in Figure 22.
[0342] Example 14
[0343] This embodiment provides a method for preparing nano-yttrium oxide, comprising the following steps:
[0344] According to Al 37.5 Zn 37.5 Y 25 The nominal formula (atomic percentage) is obtained by melting commercially available Al raw materials, Zn raw materials, and Y raw materials containing O, which is mainly composed of Al 37.5 Zn 37.2 Y 24.8 O 0.5 The alloy melt is prepared into a molten alloy with a thickness of 25 μm by a copper roller strip solidification method. The main components are Al 37.5 Zn 37.2 Y 24.8 O 0.5 The solidified structure of the initial alloy strip is mainly composed of YAl3 and YZn3 intermetallic compounds.
[0345] At normal pressure, Al 37.5 Zn 37.2 Y 24.8 O 0.5 The initial alloy strip reacts with a mixed aqueous solution of NaOH and KOH and is stirred continuously; wherein the OH in the mixed solution - The concentration of NaOH is 7 mol / L, the temperature is 110℃~115℃, and the volume of the mixed aqueous solution of NaOH and KOH is Al 37.5 Zn 37.2 Y 24.8 O 0.5 The volume of the initial alloy strip is about 50 times that of the initial alloy strip. Within 2 minutes, the hydrogen evolution reaction is completed, and the initial alloy powder is nano-fragmented through hydrogen evolution to remove Al and Zn, and simultaneously undergoes shape and composition reconstruction to generate a nano-scale Y-containing solid product.
[0346] 5 minutes after the start of the reaction, the Y-containing solid product was separated from the alkaline solution, washed, and dried to obtain nano-Y oxide powder, which was mainly crystalline, with a shape of mainly granules and short rods, and a particle size of 5nm to 300nm; the aspect ratio of the short rod particles was 1:1 to 5:1.
[0347] Example 15
[0348] This embodiment provides a method for preparing nano-gadolinium oxide, comprising the following steps:
[0349] According to Al 67 Gd 33 The nominal formula (atomic percentage) is obtained by smelting commercially available Si-containing Al raw materials, Zn raw materials, and O-containing Gd raw materials to obtain a main component of Al 67 Gd 32.3 O0.5 Si 0.2 The alloy melt is prepared into a molten alloy with a thickness of 25 μm by a copper roller strip solidification method. The main components are Al 67 Gd 32.3 O 0.5 Si 0.2 The initial alloy strip has a solidification structure mainly composed of GdAl2 intermetallic compounds.
[0350] Under normal pressure, 0.5g of the Al 67 Gd 32.3 O 0.5 Si 0.2 The initial alloy strips reacted with 50 mL of a 10 mol / L NaOH solution at its boiling point (~119°C) at atmospheric pressure with constant stirring. Within 1 minute, the hydrogen evolution reaction (HER) was complete, and the initial alloy powder was nano-fragmented by the HER-induced Al removal reaction. Simultaneously, the shape and composition of the nano-scale Gd-containing solid product was reconstructed.
[0351] Two minutes after the start of the reaction, the Gd-containing solid product was separated from the alkaline solution, washed, and dried to obtain nano-Gd oxide powder, which was mainly crystalline. Its XRD spectrum is shown in Figure 23; its shape was mainly granular and short rod-shaped, with a particle size range of 5 nm to 300 nm, and the aspect ratio of the short rod-shaped particles was 1:1 to 5:1. Its TEM morphology and diffraction pattern are shown in Figure 24.
[0352] Example 16
[0353] This embodiment provides a method for preparing nano-chromium oxide, comprising the following steps:
[0354] According to Al 80 Cr 20 The nominal formula (atomic percentage) is obtained by melting commercially available Si-containing Al raw materials and Cr raw materials to obtain a Si-containing Al raw material. 0.25 Al 80 Cr 19.75 The alloy melt is prepared into a molten alloy with a thickness of 25 μm by a copper roller strip solidification method. The main components are Si 0.25 Al 80 Cr 19.75 The solidified structure of the initial alloy strip is mainly composed of Al4Cr intermetallic compounds.
[0355] At normal pressure, Si 0.25 Al 80 Cr 19.75The initial alloy strips were reacted with NaOH aqueous solution and assisted by 40kHz ultrasonic treatment; wherein, the concentration of NaOH solution was 15mol / L, the temperature was 60℃, and the volume of NaOH solution was Si 0.25 Al 80 Cr 19.75 The volume of the initial alloy strip is about 100 times that of the initial alloy strip. Within 6 minutes, the hydrogen evolution de-Al reaction is completed, and the initial alloy is nano-fragmented by the hydrogen evolution de-Al reaction, and at the same time, the shape and composition are reconstructed to form a solid flocculent product.
[0356] 8 minutes after the start of the hydrogen evolution de-Al reaction, the solid flocculent product was separated from the solution, and after washing and drying, low-crystallinity nano-chromium oxide was obtained, which was mainly amorphous nano-chromium oxide or amorphous chromium hydroxide. Among them, the morphology of the nano-chromium oxide was mainly composed of extremely fine flocculent microstructures with a size range of 1.0 nm to 15 nm, as shown in Figure 25.
[0357] Example 17
[0358] This embodiment provides a method for preparing nano-chromium oxide, comprising the following steps:
[0359] According to Al 80 Cr 20 The nominal formula (atomic percentage) is obtained by melting commercially available Si-containing Al raw materials and Cr raw materials to obtain a Si-containing Al raw material. 0.25 Al 80 Cr 19.75 The alloy melt is prepared into a molten alloy with a thickness of 25 μm by a copper roller strip solidification method. The main components are Si 0.25 Al 80 Cr 19.75 The solidified structure of the initial alloy strip is mainly composed of Al4Cr intermetallic compounds.
[0360] At normal pressure, 0.25 g Si 0.25 Al 80 Cr 19.75 The initial alloy strip and 50 ml of a NaOH aqueous solution at a temperature of 30° C. were placed in a reactor and mixed, and the reactor was sealed; and when the reactor was sealed, the hydrogen evolution and Al removal reaction was in slow progress.
[0361] After sealing, the reactor and its interior are heated to 250°C and maintained at this temperature for 20 minutes. In this sealed environment, the pressure within the reactor is higher than atmospheric pressure, derived from the high-temperature, sealed environment and the partial pressure provided by the hydrogen produced by the reaction. After 20 minutes of insulation, the temperature and pressure are lowered, and the product within the reactor is subjected to solid-liquid separation. After cleaning and drying, the modified nano-chromium oxide is obtained. The modified nano-chromium oxide is primarily crystalline, with a morphology primarily consisting of granules and short rods. The granules have a particle size range of 2nm-50nm, the short rods have a diameter range of 2nm-30nm, and an aspect ratio of 1:1 to 5:1.
[0362] Obviously, after the reaction system is sealed, the hydrogen evolution and dehydrogenation reaction will be completely completed during the period when the temperature of the reactor and its interior is increased from 30°C to 250°C. The solid intermediate product obtained at this time must have undergone changes in morphology and / or composition compared to the final product after subsequent heating to 250°C and holding for 20 minutes. This process is called morphological and / or compositional modification.
[0363] Example 18
[0364] This embodiment provides a method for preparing nano-niobium / tantalum oxide, comprising the following steps:
[0365] According to Al 75 Nb 20 The nominal formula of Ta5 (atomic percentage) is obtained by melting commercially available Al raw materials, Nb raw materials, and Ta raw materials. The main components are Al 75 Nb 20 The alloy melt of Ta5 was prepared by copper roller strip solidification method to a thickness of 25 μm. The main components were Al 75 Nb 20 The solidified structure of the initial Ta5 alloy strip is mainly composed of Al3Nb(Ta) intermetallic compounds.
[0366] At normal pressure, Al 75 Nb 20 The Ta5 initial alloy strips were reacted with a NaOH aqueous solution with continuous stirring; wherein the concentration of the NaOH solution was 10 mol / L, the temperature was its boiling point at atmospheric pressure (~119°C), and the volume of the NaOH solution was Al 75 Nb 20 The volume of the initial Ta5 alloy ribbon is about 50 times that of the original one. Within 1 minute, the hydrogen evolution reaction ends, and the initial alloy ribbon is nano-fragmented by the hydrogen evolution and de-Al reaction. At the same time, the shape and composition are reconstructed to form a nano-scale solid product containing Nb / Ta.
[0367] 2 minutes after the start of the reaction, the obtained solid product containing Nb / Ta is separated from the alkaline solution, washed and dried to obtain a powder mainly composed of low-crystallinity nano-oxidized Nb / Ta, which is mainly flocculent in shape and has a particle size range of 1nm to 15nm.
[0368] The low-crystallinity nano-Nb / Ta oxide is heat-treated at 750° C. for 2 hours to obtain crystalline nano-Nb / Ta oxide with a particle size of 3 nm to 200 nm.
[0369] Example 19:
[0370] This embodiment provides a method for preparing nano-chromium oxide, comprising the following steps:
[0371] According to Al 80 Cr 20 The nominal formula (atomic percentage) is obtained by melting commercially available Si-containing Al raw materials and Cr raw materials to obtain a Si-containing Al raw material. 0.25 Al 80 Cr 19.75 The alloy melt is prepared into a molten alloy with a thickness of 25 μm by a copper roller strip solidification method. The main components are Si 0.25 Al 80 Cr 19.75 The solidified structure of the initial alloy strip is mainly composed of Al4Cr intermetallic compounds.
[0372] Under normal pressure, 0.5g of the Si 0.25 Al 80 Cr 19.75 The initial alloy strips were placed in a sealed container with 50 ml of 10 mol / L NaOH aqueous solution. Initially, the initial alloy strips were not in contact with the alkaline solution.
[0373] The temperature in the sealed container, as well as the temperature of the initial alloy strip and the alkaline solution, is raised to 150°C. At this time, the sealed container is in a high pressure state. Then, the Si 0.25 Al 80 Cr 19.75 The initial alloy strips are mixed with the alkaline solution at this temperature to cause a violent hydrogen evolution and de-T reaction. 0.25 Al 80 Cr 19.75 The initial alloy strips are nano-fragmented through violent hydrogen evolution and de-Al reaction during the high temperature and high pressure reaction process, and are simultaneously reconstructed in shape and composition to form solid flocculent products.
[0374] The hydrogen evolution and Al removal reaction was completed within 10 seconds. After 10 seconds, the sealed container and the reaction system were placed in cooling water and rapidly cooled to near room temperature. At the same time, the pressure in the sealed container was reduced to atmospheric pressure.
[0375] After the temperature of the reaction system is lowered to room temperature and pressure, the solid flocculent product is separated from the alkaline solution, and after washing and drying, low-crystallinity nano-chromium oxide is obtained, which is mainly amorphous nano-chromium oxide or amorphous chromium hydroxide. The morphology of the nano-chromium oxide is mainly composed of extremely fine flocculent microstructures, and the size of the flocculent microstructures ranges from 1.0 nm to 15 nm.
[0376] Comparative Example 1:
[0377] According to Al 75 Nb 25 The nominal formula (atomic percentage) is obtained by smelting commercially available Al raw materials containing Si and O with Nb raw materials, which mainly consists of Al 74.5 Nb 25 O 0.3 Si 0.2 The alloy melt is prepared into Al 74.5 Nb 25 O 0.3 Si 0.2 The alloy ingot is mainly composed of a NbAl3 intermetallic compound phase. The alloy ingot is further crushed into an initial alloy powder with an average particle size of about 25 μm by a mechanical crushing method.
[0378] Under normal pressure, the above-mentioned initial alloy powder is reacted with a 10 mol / L NaOH solution at a temperature of 25°C for 2h (the average propulsion rate of the reaction interface is less than 0.5 μm / min), and the resulting product is mainly nanoporous oxidized Nb or nanoporous Nb, as shown in Figure 26. It can be seen that under the reaction conditions, the shape of the original initial alloy powder before and after the reaction remains roughly unchanged, and it is still the original crushed and angular powder particles, and its microstructure does not undergo nano-fragmentation, nor does it generate a large amount of dispersed nano-oxide powder. Instead, it generates coarse powder particles with original angular corners composed of a nanoporous network structure, and its particle size is still comparable to that of the initial alloy powder. Therefore, the reaction of the initial alloy with the alkaline solution at a lower temperature is completely different from the reaction at a higher temperature, especially preferably near the boiling point, and the product morphology is also completely different.
[0379] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0380] The above-described embodiments merely represent several implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art could make various modifications and improvements without departing from the spirit of the present application, all of which fall within the scope of protection of the present application. Therefore, the scope of protection of the present patent application shall be determined by the appended claims.
Claims
1. A method for preparing nano metal oxides, characterized in that: The steps include: Step 1: Provide an initial alloy, the initial alloy containing elements of type M, type T, and type A; wherein, the elements of type M include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu; the elements of type T include at least one of Al, Zn; the elements of type A include at least one of O, H, Na, K, Mg, Ca, Li, Si; the composition of the initial alloy is mainly A x T y M z , where x, y, z are the atomic percentage contents of the corresponding types of elements, and 0 ≤ x ≤ 15%, 40% ≤ y ≤ 95%, 5% ≤ z ≤ 60%, x < z; the solidified structure of the initial alloy is mainly composed of M-T intermetallic compounds; Step 2: The initial alloy undergoes a hydrogen evolution and de-Ti reaction with an alkaline solution, and the temperature and concentration of the alkaline solution are controlled so that the reaction interface advances inward from the surface of the initial alloy at an average rate of not less than 2 μm / min during the reaction. During the reaction, the initial alloy undergoes nano-fragmentation through the hydrogen evolution and de-Ti reaction, and the shape and composition are reconstructed to generate a nano-scale M-containing solid product; and the shape of the M-containing solid product has a size of at least one dimension in the three-dimensional direction not exceeding 500 nm. Step 3: After the hydrogen evolution and de-T reaction is completed, the M-containing solid product in the reaction system is collected to obtain nano-oxidation M, wherein the nano-oxidation M includes at least one of low-crystallinity nano-oxidation M, crystalline nano-oxidation M, and hydrated nano-oxidation M; wherein the hydrated nano-oxidation M specifically refers to nano-hydroxylated M; the shape of the nano-oxidation M has at least one dimension in the three-dimensional direction not exceeding 500 nm.
2. The method for preparing a nano-metal oxide according to claim 1, wherein: 0<x≤15%。 3. The method for preparing a nano-metal oxide according to claim 1, wherein: The temperature of the alkaline solution is T1, and T1 ≥ 60°C.
4. The method for preparing a nano-metal oxide according to claim 3, wherein: 100℃ <T1≤T f溶液 , where T f溶液 It is the boiling point temperature of the alkaline solution participating in the reaction under normal pressure.
5. The method for preparing a nano-metal oxide according to claim 1, wherein: Ultrasound is applied during the hydrogen evolution and de-T reaction to further enhance the nano-fragmentation effect and reaction rate through ultrasonic treatment, and the frequency of the ultrasound is 20kHz to 10kHz. 6 kHz.
6. The method for preparing a nano-metal oxide according to claim 1, wherein: The shape of the nano-oxidation M includes at least one of a film, a particle, a plate, a strip, a tube, a rod, and a floc.
7. A method for preparing nano metal oxides, characterized in that: The nano-oxide M prepared by the preparation method of claim 1 is subjected to heat treatment to obtain nano-oxide M with improved crystallinity.
8. A method for preparing nano metal oxides, characterized in that: The steps include: Step 1: Provide an initial alloy, the initial alloy containing elements of type M, type T, and type A; wherein, the elements of type M include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu; the elements of type T include at least one of Al, Zn; the elements of type A include at least one of O, H, Na, K, Mg, Ca, Li, Si; the composition of the initial alloy is mainly A x T y M z , where x, y, z are the atomic percentage contents of the corresponding types of elements, and 0 ≤ x ≤ 15%, 40% ≤ y ≤ 95%, 5% ≤ z ≤ 60%, x < z; the solidification structure of the initial alloy is mainly composed of M-T intermetallic compounds; Step 2: mixing the initial alloy with an alkaline solution at a temperature of T1; wherein T s溶液 <T1≤T f溶液 , T f溶液 T is the boiling point of the alkaline solution involved in the reaction under normal pressure; s溶液 is the freezing point temperature of the alkaline solution participating in the reaction under normal pressure; Step 3: placing the mixture of the initial alloy and the alkaline solution in a sealed container, and then treating it at a temperature T2 higher than normal pressure for a period of time, collecting the product, and obtaining a nano-oxide M having a modified morphology and (or) composition compared to that before the high-pressure treatment; wherein T2>T f溶液 ; The nano-oxide M includes at least one of low-crystallinity nano-oxide M, crystalline nano-oxide M, and hydrated nano-oxide M; wherein, hydrated nano-oxide M specifically refers to nano-hydroxylated hydrated ...
9. A nano metal oxide, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8, and its specific characteristics include: the nano metal oxide is nano oxide M, and the M-type elements include at least one of Cr, V, Nb, Ta, W, Mo, Mn, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; the nano oxide M includes at least one of low-crystallinity nano oxide M, crystalline nano oxide M, and hydrated nano oxide M; wherein the hydrated nano oxide M specifically refers to nano hydroxide M; the shape of the nano oxide M has at least one dimension in the three-dimensional direction that does not exceed 500 nm.
10. A crystalline nano-chromium oxide, characterized in that: Prepared by the preparation method according to claim 7, wherein the M-type element is mainly Cr, the particle size range of the crystalline nano-chromium oxide is 3nm to 150nm, and after heat treatment and crystallization, the individual particles of the crystalline nano-chromium oxide particles still have good particle dispersion or looseness, so that they can be further crushed and refined along the grain boundaries by subsequent sand milling and ball milling, thereby obtaining ultrafine spherical or nearly spherical nano-chromium oxide particles.
11. Application of the product prepared by the preparation method according to any one of claims 1 to 8 in composite materials, catalytic materials, ceramic materials, refractory materials, advanced electronic materials, battery materials, color-changing materials, absorbing materials, sewage degradation materials, bactericidal materials, coatings, pigments, thermal spray materials, and sensors.